Toner, toner storage unit, developer, and image forming apparatus

A toner composition with crystalline polyester resin and a specific glass transition temperature structure addresses the challenges of high-temperature and humid environments, ensuring low-temperature fixing and heat-resistant preservation, and preventing toner aggregation and filming, thereby maintaining image quality in ultra-high-speed print systems.

JP2025016176APending Publication Date: 2025-01-31RICOH CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023119283
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-31

AI Technical Summary

Technical Problem

Conventional toner production methods face challenges in achieving high-level low-temperature fixing and heat-resistant preservation, leading to issues such as toner aggregation in high-temperature and humid environments, paper discharge blocking, and poor image quality in ultra-high-speed print systems.

Method used

A toner composition containing crystalline polyester resin and a sea-island phase-separated structure with non-dissolved resin and wax, along with specific glass transition temperatures and silica content, is developed to balance low-temperature fixing and heat-resistant preservation, preventing toner filming and ensuring image quality.

Benefits of technology

The solution provides a toner that effectively balances low-temperature fixing and heat-resistant preservation, preventing toner aggregation and filming, while maintaining image quality under severe environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016176000003
    Figure 2025016176000003
  • Figure 2025016176000004
    Figure 2025016176000004
  • Figure 2025016176000005
    Figure 2025016176000005
Patent Text Reader

Abstract

To provide a toner that achieves both low temperature fixability and heat-resistant storage properties, can prevent graininess and filming of additives, and can prevent an abnormal image.SOLUTION: A toner for electrostatic charge image development comprises a toner base and an external additive. The toner base contains at least a binder resin, a coloring agent, and a mold release agent. The external additive contains silica. The toner includes a component insoluble in THF and a component soluble in THF. The isolation ratio A (mass%) of silica from the toner after treatment of the following condition is performed satisfies the relational expression of [0.20≤A<0.55]. The component insoluble in THF of the toner has a glass transition temperature (Tg1st) in the first heating obtained from DSC observed in two portions, Tga1st and Tgb1st. Tga1st is -40°C or more and 10°C or less. Tgb1st is 45°C or more and 65°C or less. (Condition) 10 g of toner and 20 g of carrier are put into a 50 mL bottle, and subsequently stirred for 60 minutes at 67 Hz by using a rocking mill.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner, a toner storage unit, a developer, and an image forming apparatus. [Background technology]

[0002] In recent years, toners are required to have smaller particle size and high-temperature offset resistance for improving the quality of output images, low-temperature fixability for energy saving, and heat-resistant storage stability that can withstand high temperatures and high humidity during storage and transportation after production. In particular, since the power consumption during fixation accounts for a large portion of the power consumption in the image forming process, improving the low-temperature fixability is extremely important.

[0003] Conventionally, toners produced by the kneading and pulverizing method have been used. However, toners produced by the kneading and pulverizing method have problems such as difficulty in reducing the particle size, insufficient quality of output images due to their irregular shape and broad particle size distribution, and high fixing energy. In addition, when wax (releasing agent) is added to improve fixing properties, toners produced by the kneading and pulverizing method are cracked at the interface of the wax during pulverization, and a large amount of wax is present on the toner surface. Therefore, while the toner has a releasing effect, it is prone to adhesion (filming) of the toner to the carrier, photoconductor, and blade, and there is a problem that the overall performance is not satisfactory.

[0004] In order to overcome the problems of the kneading and pulverizing method, a method for producing a toner by a polymerization method has been proposed. The toner produced by the polymerization method can be easily made small in particle size, has a sharper particle size distribution than the toner produced by the kneading and pulverizing method, and can also include a release agent.

[0005] As a method for producing a toner by a polymerization method, a method for producing a toner from an elongation reaction product of a urethane-modified polyester as a toner binder has been disclosed for the purpose of improving low-temperature fixing properties and high-temperature offset resistance (see, for example, Patent Document 1).

[0006] Also, a method for producing a toner that is excellent in powder fluidity and transferability when made into a small particle size toner, and is also excellent in heat-resistant storage stability, low-temperature fixability, and high-temperature offset resistance has been disclosed (for example, see Patent Documents 2 and 3). Also, a method for producing a toner that produces a toner binder with a stable molecular weight distribution and has an aging process for achieving both low-temperature fixability and high-temperature offset resistance has been disclosed (for example, see Patent Documents 4 and 5). However, the above techniques do not satisfy the high level of low-temperature fixability that has been demanded in recent years.

[0007] In order to obtain a high level of low-temperature fixability, a toner containing a resin including a crystalline polyester resin and a release agent, in which the resin and the wax are incompatible with each other and have a sea-island phase-separated structure, has been proposed (see, for example, Patent Document 6). Also, a toner containing a crystalline polyester resin, a release agent, and a graft polymer has been proposed (see, for example, Patent Document 7).

[0008] Further, toners that contain a specific amorphous polyester resin and a crystalline polyester resin and have excellent low-temperature fixability, heat-resistant storage stability, and high-temperature / high-humidity storage stability have been proposed (see, for example, Patent Documents 8 to 11). Summary of the Invention [Problem to be solved by the invention]

[0009] The above-mentioned conventional technology can achieve low-temperature fixing because crystalline polyester resin melts more rapidly than amorphous polyester resin. However, in the case of toner containing crystalline polyester resin, there is a problem that toner aggregates in a high-temperature and high-humidity environment. In addition, in recent years, there have been problems such as the problem that when the toner is fixed on the surface of paper and stacked on the paper discharge tray, the toner and paper adhere to each other due to the pressure due to the weight of the paper and the residual heat during fixing (paper discharge blocking), and the image defect (graininess) caused by toner deterioration caused by the toner being subjected to stress in the developing device.

[0010] Furthermore, the toner used in today's ultra-high speed printing systems must be able to continue to output images of a consistent quality even under harsh operating conditions, such as fluctuations in temperature and humidity in the image forming device's operating environment and the continuous printing of large numbers of images. It must also be able to adapt to a variety of paper types, as a wide range of papers are used.

[0011] An object of the present invention is to provide a toner which can achieve both low-temperature fixability and heat-resistant storage stability, can suppress graininess and filming of external additives, and can suppress abnormal images. [Means for solving the problem]

[0012] A toner for developing an electrostatic image, comprising a toner base and an external additive attached to a surface of the toner base, The toner matrix contains at least a binder resin, a colorant, and a release agent, The external additive contains at least silica, The toner contains a component insoluble in THF and a component soluble in THF, a silica liberation rate A (mass%) from the toner after the treatment under the following conditions satisfies the following relational expression (1), The components of the toner that are insoluble in tetrahydrofuran (THF) are observed at two points, Tga1st and Tgb1st, in the first temperature rise of differential scanning calorimetry (DSC), The toner for developing electrostatic images, wherein the Tga1st is -40°C or more and 10°C or less, and the Tgb1st is 45°C or more and 65°C or less. 0.20≦A<0.55 (1) (conditions) 10 g of the toner and 20 g of the carrier are placed in a 50 mL bottle, and then stirred at 67 Hz for 60 minutes using a rocking mill. Effect of the Invention

[0013] According to the present invention, it is possible to provide a toner which has both low-temperature fixability and high-temperature storage stability and is capable of suppressing graininess and filming of external additives. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a diagram for explaining how to determine Tg in a DSC curve. [Diagram 2] 1 is a schematic diagram illustrating an example of an image forming apparatus according to the present invention. [Diagram 3] FIG. 2 is a schematic diagram illustrating an example of a process cartridge. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The toner, developer, and image forming apparatus according to the present invention will be described below with reference to the drawings. Note that the present invention is not limited to the following embodiments, and may be modified within the scope of what a person skilled in the art can imagine, such as other embodiments, additions, modifications, deletions, etc., and any embodiment is within the scope of the present invention as long as it achieves the functions and effects of the present invention.

[0016] (toner) The toner of the present invention is an electrostatic image developing toner comprising a toner base and an external additive attached to the surface of the toner base. The toner base contains at least a binder resin, a colorant, and a release agent, and the external additive contains at least silica. The toner contains a component insoluble in THF and a component soluble in THF, and a silica liberation rate A (mass %) from the toner after treatment under the following conditions satisfies the following relational expression (1). The tetrahydrofuran (THF)-insoluble components of the toner are observed to have two glass transition temperatures (Tg1st) in the first heating step of differential scanning calorimetry (DSC), Tga1st and Tgb1st, and the Tga1st is from -40°C to 10°C, and the Tgb1st is from 45°C to 65°C. 0.20≦A<0.55 (1) (conditions) 10 g of the toner and 20 g of the carrier are placed in a 50 mL bottle, and then stirred at 67 Hz for 60 minutes using a rocking mill. The method for measuring the silica liberation rate A (mass %) from the toner in the present invention will be described later.

[0017] The THF-insoluble component is preferably a polyester resin, and the components contributing to the two glass transition temperatures Tga1st and Tgb1st in the first temperature rise in DSC are designated as polyester resin A and polyester resin B, respectively. Further, a component that contributes to the glass transition temperature (Tgc2nd) at the second temperature rise of the DSC of the THF-soluble component of the toner is designated as polyester resin C. Polyester resin A and polyester resin B are components derived from a large amorphous polyester resin having a weight average molecular weight (Mw) of 100,000 to 200,000, and the THF-soluble polyester resin C is a component derived from an amorphous polyester resin having a weight average molecular weight (Mw) of 3,000 to 10,000.

[0018] In the present invention, the glass transition temperature is defined as follows. Tg1st: glass transition temperature of the toner at the first temperature rise Tg2nd: glass transition temperature of the toner at the second heating Tga1st: glass transition temperature of the THF insoluble component in the toner at the first temperature rise Tgb1st: Glass transition temperature of the THF insoluble component in the toner at the first temperature rise Tga2nd: The second glass transition temperature of the THF insoluble components in the toner Tgb2nd: The second glass transition temperature of the THF insoluble components in the toner Tgab2nd: The glass transition temperature of the THF insoluble component (mixed component) in the toner after the second heating Tgc2nd: The glass transition temperature of the THF-soluble component in the toner after the second heating.

[0019] In addition, unless otherwise specified, the melting points and glass transition temperatures Tg of the polyester resins A, B, and C, the release agent, and other constituent components are the endothermic peak top temperature and glass transition temperature Tg2nd during the second heating, respectively, of each sample.

[0020] Polyester resin A imparts plasticity to the toner. The polyester resin A in the toner of the present invention, which is insoluble in tetrahydrofuran (THF), lowers the Tg and melt viscosity and ensures low-temperature fixability, and has a branched structure in the molecular skeleton and a three-dimensional network structure in the molecular chain, so that the toner has rubber-like properties in that it deforms at low temperatures but does not flow.

[0021] Conventional techniques (e.g., Patent Document 8) have attempted to solve the problem by optimizing the ratio of polyester resin A and polyester resin C. However, if too much polyester resin A is added, Tg decreases and storage stability cannot be guaranteed. In addition, the stress resistance of the toner deteriorates, and the fluidizing agent on the toner surface is buried due to the thermal and mechanical stress caused by stirring in the developing device, and the adhesion of the toner particles increases. As a result, there is a concern that defects such as image blurring may occur in the transfer process. On the other hand, if the amount of polyester resin A is too small, the plasticity is not imparted sufficiently and low-temperature fixability cannot be satisfied. In addition, there is a concern that the necessary elasticity is not imparted, high-temperature offset is deteriorated, the fixable area is narrowed, and the image glossiness is too high.

[0022] In the present invention, by using polyester resin B, which has a Tg similar to that of the toner and does not deviate significantly from that of the toner, and which provides elasticity, it is possible to provide elasticity while maintaining the Tg, ensure the offset range, and control the image gloss in an appropriate range while preventing image graininess. However, although the cause is unclear, it was found that when the resin components are mixed in an arbitrary ratio, the resin separates, causing poor pigment dispersion and reducing the coloring degree. It was found that by determining polyester resins A, B, and C so that the component ratio is appropriate, it is possible to ensure the fixing range and storage stability without reducing the coloring degree, and a better toner can be obtained.

[0023] In addition, when preparing the oil phase, the raw materials constituting the oil phase can be arranged finely and uniformly in the oil droplets by adding a homogenization process in addition to the conventional dissolving process, and the desired granulation properties can be obtained even if the amount of surfactant used in toner production is reduced. Furthermore, when produced with a reduced amount of surfactant, a certain amount of surfactant remains on the toner surface, which improves low-temperature fixability. In addition, by adding hot water washing to the toner washing process, the surface hardness is improved by annealing the toner surface, so that excessive embedding of external additives can be suppressed, and abnormal images can be further suppressed. The above technology allows low-temperature fixability and heat-resistant storage stability to be achieved without impairing the properties of the polyester resins A, B, and C.

[0024] <Polyester resin A> Polyester resin A is a resin insoluble in tetrahydrofuran (THF). The polyester resin A preferably contains, as its constituent components, a polyhydric alcohol component and a polyvalent carboxylic acid component, and the polyhydric alcohol component is preferably a diol component.

[0025] The diol component includes, for example, an aliphatic diol having 3 or more and 10 or less carbon atoms. Examples of the aliphatic diols having 3 to 10 carbon atoms include 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol. The content of an aliphatic diol having 3 to 10 carbon atoms is preferably 50 mol % or more, and more preferably 80 mol % or more.

[0026] The diol component of the polyester resin A preferably has an odd carbon number of 3 to 9 in the main chain and an alkyl group in the side chain, and more preferably has a structure represented by the following general formula (I). HO-(CR 1 R 2 )n-OH General formula (I)

[0027] In the above formula, R 1 and R 2 each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. n represents an odd number from 3 to 9. In the n repeating units, R1 and R2 may be the same or different.

[0028] In addition, the polyester resin A preferably contains a crosslinking component. As the crosslinking component, it is preferable to contain a trihydric or higher aliphatic alcohol component, and from the viewpoint of the gloss and image density of the fixed image, it is more preferable to contain a trihydric or tetrahydric aliphatic alcohol component. As the trihydric or tetrahydric aliphatic alcohol component, it is preferable to use a trihydric or tetrahydric aliphatic polyhydric alcohol component having 3 to 10 carbon atoms. The crosslinking component may be only the trihydric or higher aliphatic alcohol.

[0029] The trihydric or higher aliphatic alcohol can be appropriately selected depending on the purpose, and examples thereof include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, dipentaerythritol, etc. These trihydric or higher aliphatic alcohols may be used alone or in combination of two or more kinds.

[0030] As the crosslinking component of polyester resin A, a trivalent or higher carboxylic acid or an epoxy compound, etc. can be used. However, from the viewpoint of preventing unevenness and obtaining sufficient gloss and image density, it is more preferable to contain a trivalent or higher aliphatic alcohol as the crosslinking component.

[0031] The proportion of the crosslinking component in the constituent components of the polyester resin A is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5% by mass or more and 5% by mass or less, and more preferably 1% by mass or more and 3% by mass or less.

[0032] The proportion of trihydric or higher aliphatic alcohol in the polyhydric alcohol component that is a constituent of polyester resin A is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 50% by mass or more and 100% by mass or less, and more preferably 90% by mass or more and 100% by mass or less.

[0033] The dicarboxylic acid component of the polyester resin A contains an aliphatic dicarboxylic acid having 4 to 12 carbon atoms, and the content of the aliphatic dicarboxylic acid is preferably 50 mol % or more. Examples of the aliphatic dicarboxylic acid having 4 to 12 carbon atoms include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid.

[0034] In addition, it is preferable that polyester resin A has a urethane bond and / or a urea bond in order to provide better adhesion to recording media such as paper, etc. This allows the urethane bond or urea bond to behave like a pseudo-crosslinking point, strengthening the rubber-like properties of polyester resin A and providing better heat-resistant storage stability and high-temperature offset resistance of the toner.

[0035] The molecular weight of polyester resin A is not particularly limited and can be appropriately selected according to the purpose. However, if the molecular weight is too low, the toner may have poor heat-resistant storage stability and poor durability against stress such as stirring in a developing machine, while if the molecular weight is too high, the toner may have high viscoelasticity when melted and poor low-temperature fixability. Therefore, it is preferable that the weight-average molecular weight (Mw) is 100,000 to 200,000 as measured by GPC (gel permeation chromatography).

[0036] The Tga2nd of the polyester resin A is -50°C or more and 0°C or less, and preferably -40°C or more and -20°C or less. If the Tga2nd is less than -50°C, the toner has poor heat-resistant storage stability and durability against stress such as stirring in a developing machine, and also has poor filming resistance. On the other hand, if the Tga2nd is more than 0°C, the toner is not deformed sufficiently by heating and pressure during fixing, and the low-temperature fixing property is insufficient.

[0037] <Polyester resin B> Polyester resin B is a resin insoluble in tetrahydrofuran (THF). The polyester resin B preferably contains a polyhydric alcohol component and a polycarboxylic acid component. The polyester resin B is preferably a modified polyester containing an ester bond and a bond unit other than the ester bond, and the binder resin precursor is preferably a resin precursor capable of producing the modified polyester.

[0038] Examples of the polyhydric alcohol component include alkylene glycols (ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, etc.); alkylene ether glycols (diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, etc.); alicyclic diols (1,4-cyclohexanedimethanol, hydrogenated bisphenol A, etc.); bisphenols (bisphenol A, bisphenol F, bisphenol S, etc.); alkylene oxide (ethylene oxide, propylene oxide, butylene oxide, etc.) adducts of the above alicyclic diols; and alkylene oxide (ethylene oxide, propylene oxide, butylene oxide, etc.) adducts of the above bisphenols, and two or more of these may be used in combination. Among these, alkylene glycols having 2 to 12 carbon atoms and alkylene oxide adducts of bisphenols (for example, bisphenol A ethylene oxide 2-mol adduct, bisphenol A propylene oxide 2-mol adduct, bisphenol A propylene oxide 3-mol adduct, etc.) are preferred.

[0039] Examples of trihydric or higher polyols include polyhydric aliphatic alcohols (glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, etc.); trihydric or higher phenols (phenol novolac, cresol novolac, etc.); alkylene oxide adducts of trihydric or higher polyphenols; and the like, and two or more of these may be used in combination.

[0040] The divalent carboxylic acid components are alkylene dicarboxylic acids (succinic acid, adipic acid, sucrose, etc.). carboxylic acids (maleic acid, fumaric acid, etc.); alkenylene dicarboxylic acids (maleic acid, fumaric acid, etc.); aromatic dicarboxylic acids (terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, etc.), etc., and two or more of them may be used in combination. Among them, alkenylene dicarboxylic acids having 4 to 20 carbon atoms and aromatic dicarboxylic acids having 8 to 20 carbon atoms are preferred.

[0041] Examples of trivalent or higher polycarboxylic acids include aromatic polycarboxylic acids having 9 to 20 carbon atoms (eg, trimellitic acid, pyromellitic acid, etc.), and two or more of them may be used in combination.

[0042] Instead of the polycarboxylic acid, anhydrides or lower alkyl esters (methyl esters, ethyl esters, isopropyl esters, etc.) of polycarboxylic acids may be used. In addition, it is preferable that polyester resin B has a urethane bond and / or a urea bond in order to provide better adhesion to recording media such as paper, whereby the urethane bond or urea bond behaves like a pseudo-crosslinking point, the rubber-like properties of polyester resin B are strengthened, and the toner has better heat-resistant storage stability and high-temperature offset resistance.

[0043] The Tgb2nd of polyester resin B is preferably 45° C. or more and 65° C. or less, more preferably 50° C. or more and 60° C. or less. When the Tgb2nd is 45° C. or more, the toner has good heat-resistant storage stability and durability against stress such as stirring in a developing machine, and the filming resistance is not deteriorated. When the Tgb2nd is 65° C. or less, the toner is sufficiently deformed by heating and pressure during fixing, and the low-temperature fixing property is sufficient.

[0044] <Polyester resin C> Polyester resin C is a resin soluble in tetrahydrofuran (THF). The polyester resin C preferably contains a diol component and a dicarboxylic acid component as constituent components, and preferably contains 40 mol % or more of alkylene glycol. The polyester resin C may or may not contain a crosslinking component as a constituent component.

[0045] The polyester resin C is preferably a linear polyester resin. Moreover, an unmodified polyester resin is preferable as the polyester resin C. The unmodified polyester resin is a polyester resin obtained using a polyhydric alcohol and a polycarboxylic acid or a derivative thereof, such as a polycarboxylic acid, a polycarboxylic acid anhydride, or a polycarboxylic acid ester, and is not modified with an isocyanate compound or the like.

[0046] Examples of the polyhydric alcohol include diols. Examples of the diol include alkylene (carbon number 2 to 3) oxide (average number of moles added: 1 to 10) adducts of bisphenol A such as polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane and polyoxyethylene(2.2)-2,2-bis(4-hydroxyphenyl)propane; ethylene glycol, propylene glycol; hydrogenated bisphenol A, and alkylene (carbon number 2 to 3) oxide (average number of moles added: 1 to 10) adducts of hydrogenated bisphenol A. These may be used alone or in combination of two or more.

[0047] Examples of the polycarboxylic acid include dicarboxylic acids. Examples of the dicarboxylic acid include adipic acid, phthalic acid, isophthalic acid, terephthalic acid, fumaric acid, maleic acid, and succinic acids substituted with an alkyl group having 1 to 20 carbon atoms or an alkenyl group having 2 to 20 carbon atoms, such as dodecenylsuccinic acid and octylsuccinic acid. In particular, it is preferable to contain 50 mol % or more of terephthalic acid. These may be used alone or in combination of two or more.

[0048] Furthermore, the polyester resin C may contain a trivalent or higher carboxylic acid and / or a trivalent or higher alcohol at the end of its resin chain in order to adjust the acid value and hydroxyl value.

[0049] Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, and acid anhydrides thereof. Examples of the trihydric or higher alcohol include glycerin, pentaerythritol, and trimethylolpropane.

[0050] In addition, the polyester resin C preferably contains a crosslinking component. As the crosslinking component, it is preferable to contain a trivalent or higher aliphatic alcohol, and from the viewpoint of the gloss and image density of the fixed image, it is more preferable to contain a trivalent or tetravalent aliphatic alcohol. As the trivalent or tetravalent aliphatic alcohol, it is preferable to use a trivalent or tetravalent aliphatic polyhydric alcohol component having 3 to 10 carbon atoms. The crosslinking component may be only the trivalent or higher aliphatic alcohol.

[0051] The trihydric or higher aliphatic alcohol can be appropriately selected depending on the purpose, and examples thereof include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, dipentaerythritol, etc. These trihydric or higher aliphatic alcohols may be used alone or in combination of two or more kinds.

[0052] As the crosslinking component of polyester resin C, a trivalent or higher carboxylic acid or an epoxy compound, etc. can be used. However, from the viewpoint of preventing unevenness and obtaining sufficient gloss and image density, it is more preferable to contain a trivalent or higher aliphatic alcohol as the crosslinking component.

[0053] The molecular weight of polyester resin C is not particularly limited and can be appropriately selected according to the purpose. However, if the molecular weight is too low, the toner may have poor heat-resistant storage stability and durability against stress such as stirring in a developing machine, and if the molecular weight is too high, the viscoelasticity of the toner when melted may increase and the low-temperature fixability may be poor. In addition, if the amount of the component having a molecular weight of 600 or less is too large, the toner may have poor heat-resistant storage stability and durability against stress such as stirring in a developing machine, and if the amount of the component having a molecular weight of 600 or less is too small, the low-temperature fixability may be poor.

[0054] Therefore, in the GPC (gel permeation chromatography) measurement, the weight average molecular weight (Mw) is preferably 3,000 to 10,000, and the number average molecular weight (Mn) is preferably 1,000 to 4,000. Also, Mw / Mn is preferably 1.0 to 4.0. Also, the weight average molecular weight (Mw) is more preferably 4,000 to 7,000, the number average molecular weight (Mn) is more preferably 1,500 to 3,000, and the Mw / Mn is more preferably 1.0 to 3.5.

[0055] The THF-soluble component having a molecular weight of 600 or less is preferably 2% by mass to 10% by mass, and polyester resin C may be purified by extracting it with methanol to remove the component having a molecular weight of 600 or less.

[0056] The acid value of the polyester resin C is not particularly limited and can be appropriately selected depending on the purpose, but is preferably from 1 mgKOH / g to 50 mgKOH / g, more preferably from 5 mgKOH / g to 30 mgKOH / g. When the acid value is 1 mgKOH / g or more, the toner tends to be negatively charged, and furthermore, the affinity between the toner and paper is improved when the toner is fixed to the paper, and low-temperature fixability can be improved. On the other hand, when the acid value is more than 50 mgKOH / g, the charging stability, particularly the charging stability against environmental changes, may decrease.

[0057] The hydroxyl value of the polyester resin C is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 5 mgKOH / g or more.

[0058] The Tgc2nd of the polyester resin C is 45° C. to 65° C., and preferably 50° C. to 60° C. If the Tgc2nd is less than 45° C., the toner has poor heat-resistant storage stability and durability against stress such as stirring in a developing machine, and also has poor filming resistance. On the other hand, if the Tgc2nd is more than 65° C., the toner is not deformed sufficiently by heating and pressure during fixing, and low-temperature fixing properties are insufficient.

[0059] The content of polyester resin C is preferably 80 parts by mass or more and 90 parts by mass or less, and more preferably 80 parts by mass or more and 85 parts by mass or less, relative to 100 parts by mass of toner. In the case of a three-component system such as polyester resin A, polyester resin B, and polyester resin C as in the present invention, although the cause is not clear, if the content of polyester resin C is less than 80 parts by mass, polyester resin A and polyester resin B may separate, deteriorating the dispersibility of the pigment in the toner and decreasing the coloring degree of the toner.

[0060] <Polyester resin having urethane bond and / or urea bond> The polyester resin having the urethane bond and / or urea bond is not particularly limited and can be appropriately selected according to the purpose. An example thereof is a reaction product of a polyester resin having an active hydrogen group and a polyisocyanate. This reaction product is preferably used as a reaction precursor (hereinafter sometimes referred to as a "prepolymer") to be reacted with a curing agent described later. Examples of the polyester resin having an active hydrogen group include polyester resins having a hydroxyl group.

[0061] -Polyisocyanate- The polyisocyanate is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyisocyanate include diisocyanates and tri- or higher valent isocyanates. Examples of the diisocyanate include aliphatic diisocyanates, alicyclic diisocyanates, aromatic diisocyanates, araliphatic diisocyanates, isocyanurates, and those blocked with phenol derivatives, oximes, caprolactams, and the like.

[0062] Examples of the aliphatic diisocyanate include tetramethylene diisocyanate, hexamethylene diisocyanate, methyl 2,6-diisocyanatocaproate, octamethylene diisocyanate, decamethylene diisocyanate, dodecamethylene diisocyanate, tetradecamethylene diisocyanate, trimethylhexane diisocyanate, and tetramethylhexane diisocyanate. Examples of the alicyclic diisocyanate include isophorone diisocyanate and cyclohexylmethane diisocyanate.

[0063] Examples of the aromatic diisocyanate include tolylene diisocyanate, diisocyanatodiphenylmethane, 1,5-naphthylene diisocyanate, 4,4'-diisocyanatodiphenyl, 4,4'-diisocyanato-3,3'-dimethyldiphenyl, 4,4'-diisocyanato-3-methyldiphenylmethane, and 4,4'-diisocyanato-diphenyl ether.

[0064] Examples of the aromatic aliphatic diisocyanate include α,α,α',α'-tetramethylxylylene diisocyanate.

[0065] Examples of the isocyanurates include tris(isocyanatoalkyl)isocyanurate, tris(isocyanatocycloalkyl)isocyanurate, and the like. These polyisocyanates may be used alone or in combination of two or more kinds.

[0066] - Hardener - The curing agent is not particularly limited as long as it reacts with the prepolymer, and may be appropriately selected depending on the purpose. For example, an active hydrogen group-containing compound may be used.

[0067] --Compounds containing active hydrogen groups-- The active hydrogen group in the active hydrogen group-containing compound is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include hydroxyl groups (alcoholic hydroxyl groups and phenolic hydroxyl groups), amino groups, carboxyl groups, mercapto groups, etc. These may be used alone or in combination of two or more.

[0068] The active hydrogen group-containing compound is preferably an amine because it can form a urea bond. Examples of the amine include diamines, trivalent or higher amines, amino alcohols, amino mercaptans, amino acids, and compounds in which the amino groups of these are blocked. These may be used alone or in combination of two or more. Among these, diamines or mixtures of diamines with small amounts of trivalent or higher amines are preferred.

[0069] Examples of the diamine include aromatic diamines, alicyclic diamines, and aliphatic diamines. Examples of the aromatic diamines include phenylenediamine, diethyltoluenediamine, and 4,4'-diaminodiphenylmethane. Examples of the alicyclic diamines include 4,4'-diamino-3,3'-dimethyldicyclohexylmethane, diaminocyclohexane, and isophoronediamine. Examples of the aliphatic diamines include ethylenediamine, tetramethylenediamine, and hexamethylenediamine.

[0070] Examples of the trivalent or higher amine include diethylenetriamine and triethylenetetramine.

[0071] Examples of the amino alcohol include ethanolamine and hydroxyethylaniline.

[0072] Examples of the amino mercaptan include aminoethyl mercaptan and aminopropyl mercaptan. Examples of the amino acid include aminopropionic acid and aminocaproic acid. Examples of the blocked amino group include ketimine compounds and oxazoline compounds obtained by blocking the amino group with ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone.

[0073] The molecular structures of the polyester resins A, B, C, etc. can be confirmed by NMR measurement in solution or solid, as well as X-ray diffraction, GC / MS, LC / MS, IR measurement, etc. -1 and 990±10cm -1 One method is to detect polyester resins that do not have absorption due to olefin δCH (out-of-plane bending vibration).

[0074] <Crystalline polyester resin D> The toner may contain crystalline polyester resin D (hereinafter referred to as crystalline polyester resin) as a crystalline resin. The crystalline polyester resin has high crystallinity and exhibits a thermal melting characteristic that shows a rapid viscosity drop near the fixing start temperature. By using a crystalline polyester resin having such characteristics together with the polyester resin, the heat-resistant storage stability due to crystallinity is good until just before the melting start temperature, and a rapid viscosity drop (sharp melt) due to melting of the crystalline polyester resin can be caused at the melting start temperature. Then, the crystalline polyester resin is compatible with the polyester resin, and both are fixed by a rapid viscosity drop, so that a toner having both good heat-resistant storage stability and low-temperature fixing ability can be obtained. In addition, the release width (the difference between the fixing lower limit temperature and the high-temperature offset occurrence temperature) also shows good results.

[0075] The crystalline polyester resin is obtained by using a polyhydric alcohol and a polycarboxylic acid such as a polycarboxylic acid, a polycarboxylic anhydride, or a polycarboxylic ester, or a derivative thereof. Note that, in the present invention, the crystalline polyester resin refers to a resin obtained by using a polyhydric alcohol and a polycarboxylic acid such as a polycarboxylic acid, a polycarboxylic anhydride, or a polycarboxylic ester, or a derivative thereof, as described above, and a modified polyester resin, for example, the prepolymer, and a resin obtained by subjecting the prepolymer to a crosslinking and / or elongation reaction, do not belong to the crystalline polyester resin.

[0076] The presence or absence of crystallinity of the crystalline polyester resin in the present invention can be confirmed by a crystal analysis X-ray diffraction device (for example, X'Pert Pro MRD, Philips). The measurement method is described below. First, the target sample is ground in a mortar to prepare a sample powder, and the obtained sample powder is evenly applied to a sample holder. After that, the sample holder is set in the diffraction device, and measurements are performed to obtain a diffraction spectrum. If the peak half-width of the peak with the highest peak intensity among the peaks obtained in the range of 20°<2θ<25° is 2.0 or less, it is determined to have crystallinity. In contrast to crystalline polyester resins, polyester resins that do not exhibit the above-mentioned state are referred to as amorphous polyester resins in the present invention.

[0077] An example of the conditions for measuring X-ray diffraction is given below. [Measurement conditions] Tension kV: 45kV Current: 40mA MPSS Upper Gonio Scan mode: continuous Start angle: 3° End angle: 35° Angle Step: 0.02° Lucident beam optics Divergence slit: Div slit 1 / 2 Diffraction beam optics Anti scatter slit: As Fixed 1 / 2 Receiving slit: Prog rec slit

[0078] -Polyhydric alcohol- The polyhydric alcohol is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyhydric alcohol include diols and trihydric or higher alcohols.

[0079] Examples of the diol include saturated aliphatic diols. Examples of the saturated aliphatic diol include linear saturated aliphatic diols and branched saturated aliphatic diols. Among these, linear saturated aliphatic diols are preferred, and linear saturated aliphatic diols having 2 to 12 carbon atoms are more preferred. If the saturated aliphatic diol is a branched type, the crystallinity of the crystalline polyester resin may decrease, resulting in a decrease in melting point. In addition, if the carbon number of the saturated aliphatic diol exceeds 12, it becomes difficult to obtain a practical material. It is more preferred that the carbon number is 12 or less.

[0080] Examples of the saturated aliphatic diol include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, 1,14-eicosanedecanediol, etc. Among these, ethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol are preferred in terms of the high crystallinity and excellent sharp melting properties of the crystalline polyester resin.

[0081] Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, etc. These may be used alone or in combination of two or more.

[0082] -Polycarboxylic acids- The polyvalent carboxylic acid is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyvalent carboxylic acid include divalent carboxylic acids and trivalent or higher carboxylic acids.

[0083] Examples of the divalent carboxylic acid include saturated aliphatic dicarboxylic acids such as oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid; and aromatic dicarboxylic acids such as dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, malonic acid, and mesaconic acid; and further, anhydrides of these acids and lower (carbon number: 1 to 3) alkyl esters of these acids.

[0084] Examples of the trivalent or higher carboxylic acid include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, and the like, as well as anhydrides and lower (carbon number 1 to 3) alkyl esters thereof.

[0085] The polycarboxylic acid may contain a dicarboxylic acid having a sulfonic acid group in addition to the saturated aliphatic dicarboxylic acid or aromatic dicarboxylic acid. Furthermore, the polycarboxylic acid may contain a dicarboxylic acid having a double bond in addition to the saturated aliphatic dicarboxylic acid or aromatic dicarboxylic acid. These may be used alone or in combination of two or more.

[0086] The crystalline polyester resin is preferably composed of a linear saturated aliphatic dicarboxylic acid having 4 to 12 carbon atoms and a linear saturated aliphatic diol having 2 to 12 carbon atoms. That is, the crystalline polyester resin preferably has a constituent unit derived from a saturated aliphatic dicarboxylic acid having a carbon number of 4 or more and 12 or less, and a constituent unit derived from a saturated aliphatic diol having a carbon number of 2 or more and 12 or less. This is preferable in that the resin has high crystallinity and excellent sharp melting properties, and can therefore exhibit excellent low-temperature fixability.

[0087] The melting point of the crystalline polyester resin is not particularly limited and may be appropriately selected depending on the purpose, but is preferably from 60° C. to 80° C. If the melting point is less than 60° C., the crystalline polyester resin is likely to melt at low temperatures, and the heat-resistant storage stability of the toner may decrease, whereas if the melting point is more than 80° C., the crystalline polyester resin is not sufficiently melted by heating during fixing, and the low-temperature fixability may decrease.

[0088] The molecular weight of the crystalline polyester resin is not particularly limited and can be appropriately selected according to the purpose. From the viewpoint that a low molecular weight resin with a sharp molecular weight distribution has excellent low-temperature fixability, and a large amount of low molecular weight components reduces heat-resistant storage stability, the crystalline polyester resin preferably has a weight average molecular weight (Mw) of 3,000 to 30,000, a number average molecular weight (Mn) of 1,000 to 10,000, and Mw / Mn of 1.0 to 10, as measured by GPC. More preferably, the weight average molecular weight (Mw) is 5,000 to 15,000, the number average molecular weight (Mn) is 2,000 to 10,000, and Mw / Mn is 1.0 to 5.0.

[0089] The acid value of the crystalline polyester resin is not particularly limited and can be appropriately selected depending on the purpose, but from the viewpoint of affinity between paper and resin, in order to achieve the desired low-temperature fixability, it is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, while in order to improve high-temperature offset resistance, it is preferably 45 mgKOH / g or less.

[0090] The hydroxyl value of the crystalline polyester resin is not particularly limited and may be appropriately selected depending on the purpose. In order to achieve the desired low-temperature fixability and good charging characteristics, the hydroxyl value is preferably 0 mgKOH / g or more and 50 mgKOH / g or less, and more preferably 5 mgKOH / g or more and 50 mgKOH / g or less.

[0091] The molecular structure of the crystalline polyester resin can be confirmed by NMR measurement of a solution or solid, as well as X-ray diffraction, GC / MS, LC / MS, IR measurement, etc. -1 Or 990±10cm -1 One method is to detect a crystalline polyester resin that has absorption based on the δCH (out-of-plane bending vibration) of olefin.

[0092] The content of the crystalline polyester resin is not particularly limited and can be appropriately selected according to the purpose, but is preferably 1 part by mass or more and 10 parts by mass or less, more preferably 2 parts by mass or more and 4 parts by mass or less, relative to 100 parts by mass of the toner. When the content is 1 part by mass or more, the sharp melting by the crystalline polyester resin is sufficient, and the low-temperature fixing property is good. In addition, when it is 10 parts by mass or less, the heat-resistant storage stability is not deteriorated, and the image is not easily fogged. When the content is within the more preferable range, it is advantageous in that both high image quality and low-temperature fixing property are excellent.

[0093] <Other ingredients> In addition to the above-mentioned components, the toner of the present invention may contain other components such as a release agent, a colorant, a charge control agent, an external additive, a flowability improver, a cleaning property improver, and a magnetic material, if necessary.

[0094] -Release agent- The release agent is not particularly limited and can be appropriately selected from known agents. Examples of wax and wax release agents include natural waxes such as vegetable waxes such as carnauba wax, cotton wax, and wood wax rice wax; animal waxes such as beeswax and lanolin; mineral waxes such as ozokerite and cerusin; and petroleum waxes such as paraffin, microcrystalline, and petrolatum. In addition to these natural waxes, examples of the wax include Fischer-Tropsch wax, synthetic hydrocarbon waxes such as polyethylene and polypropylene, and synthetic waxes such as esters, ketones and ethers.

[0095] Further, fatty acid amide compounds such as 12-hydroxystearic acid amide, stearic acid amide, phthalimide anhydride, and chlorinated hydrocarbons; homopolymers or copolymers of polyacrylates such as poly-n-stearyl methacrylate and poly-n-lauryl methacrylate, which are low molecular weight crystalline polymer resins (for example, a copolymer of n-stearyl acrylate and ethyl methacrylate); and crystalline polymers having long alkyl groups in their side chains may be used. Among these, hydrocarbon waxes such as paraffin wax, microcrystalline wax, Fischer-Tropsch wax, polyethylene wax, and polypropylene wax are preferred.

[0096] The melting point of the release agent is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 60° C. or more and 80° C. or less. When the melting point is 60° C. or more, the release agent does not melt at low temperatures and has good heat resistance storage stability. In addition, when the resin melts and is in the fixing temperature range, the release agent melts sufficiently, so that fixing offset does not occur and image defects do not occur.

[0097] The content of the release agent is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 2 to 10 parts by mass, more preferably 3 to 8 parts by mass relative to 100 parts by mass of the toner. By having a content of 2 parts by mass or more, high-temperature offset resistance and low-temperature fixability during fixing are improved. In addition, by having a content of 10 parts by mass or less, the heat-resistant storage stability is not reduced and image fogging does not occur. If the content is within the above more preferred range, it is advantageous in terms of improving image quality and fixing stability.

[0098] -Coloring agent- The colorant is not particularly limited and can be appropriately selected depending on the purpose. Examples include carbon black, nigrosine dye, iron black, naphthol yellow S, Hansa yellow (10G, 5G, G), cadmium yellow, yellow iron oxide, yellow ochre, yellow lead, titanium yellow, polyazo yellow, oil yellow, Hansa yellow (GR, A, RN, R), pigment yellow L, benzidine yellow (G, GR), permanent yellow (NCG), Balkan fast yellow (5G, R), tartrazine lake, quinoline yellow lake, anthrazan yellow BGL, isoindolinone yellow, red iron oxide, red lead, vermilion, cadmium red Cadmium Mercury Red, Antimony Vermilion, Permanent Red 4R, Para Red, Phaysee Red, Parachlor Orthonitroaniline Red, Lithol Fast Scarlet G, Brilliant Fast Scarlet, Brilliant Carmine BS, Permanent Red (F2R, F4R, FRL, FRLL, F4RH), Fast Scarlet VD, Belcan Fast Rubin B, Brilliant Scarlet G, Lithol Rubin GX, Permanent Red F5R, Brilliant Carmine 6B, Pigment Scarlet 3B, Bordeaux 5B, Toluigi Bon Maroon, Permanent Bordeaux F2K, Helio Bordeaux BL, Bordeaux 10B, Bon Maroon Light, Bon Maroon Medium, Eosin Lake, Rhodamine Lake B, Rhodamine Lake Y, Alizarin Lake, Thioindigo Red B, Thioindigo Maroon, Oil Red, Quinacridone Red, Pyrazolone Red, Polyazo Red, Chrome Vermilion, Benzidine Orange, Perinone Orange, Oil Orange, Cobalt Blue, Cerulean Blue, Alkaline Blue Lake, Peacock Blue Lake, Victoria Blue Lake, Metal-free Phthalosyl Anthracite Blue, Phthalocyanine Blue, Fast Sky Blue, Indanthrene Blue (RS, BC), Indigo, Ultramarine Blue, Prussian Blue, Anthraquinone Blue, Fast Violet B, Methyl Violet Lake, Cobalt Purple, Manganese Purple, Dioxane Violet, Anthraquinone Violet, Chrome Green, Zinc Green, Chromium Oxide, Pyridian, Emerald Green, Pigment Green B, Naphthol Green B, Green Gold, Acid Green Lake, Malachite Green Lake, Phthalocyanine Green, Anthraquinone Green,Examples include titanium oxide, zinc oxide, and lithopone.

[0099] The content of the colorant is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 part by mass to 15 parts by mass, more preferably 3 parts by mass to 10 parts by mass, based on 100 parts by mass of the toner.

[0100] The colorant can also be used as a masterbatch composited with a resin. Examples of the resin used to manufacture the masterbatch or the resin kneaded with the masterbatch include, in addition to the polyester resin, styrene or a polymer of a substitute thereof, such as polystyrene, poly-p-chlorostyrene, or polyvinyltoluene; styrene-p-chlorostyrene copolymer, styrene-propylene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-methyl acrylate copolymer, styrene-ethyl acrylate copolymer, styrene-butyl acrylate copolymer, styrene-octyl acrylate copolymer, styrene-methyl methacrylate copolymer, styrene-ethyl methacrylate copolymer, styrene-butyl methacrylate copolymer, styrene-α-chloromethyl ... styrene-based copolymers such as styrene-acrylonitrile copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-acrylonitrile-indene copolymers, styrene-maleic acid copolymers, and styrene-maleic acid ester copolymers; polymethyl methacrylate, polybutyl methacrylate, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, polyester, epoxy resins, epoxy polyol resins, polyurethane, polyamide, polyvinyl butyral, polyacrylic acid resins, rosin, modified rosin, terpene resins, aliphatic or alicyclic hydrocarbon resins, aromatic petroleum resins, chlorinated paraffin, and paraffin wax. These may be used alone or in combination of two or more.

[0101] The master batch can be obtained by mixing and kneading the resin for the master batch and the colorant under high shear force. In this case, an organic solvent can be used to enhance the interaction between the colorant and the resin. In addition, a method called a flushing method, in which an aqueous paste containing water of the colorant is mixed and kneaded with the resin and the organic solvent to transfer the colorant to the resin side and remove the water and organic solvent components, is also preferable because it does not require drying since the wet cake of the colorant can be used as it is. A high shear dispersion device such as a three-roll mill is preferably used for mixing and kneading.

[0102] -Charge control agent (modified layered inorganic minerals)- The modified layered inorganic mineral used in the toner of the present invention is not particularly limited, but is preferably one having a basic smectite crystal structure modified with an organic cation. In addition, when the layered inorganic mineral is a hydrotalcite, a part of the divalent metal is replaced with a trivalent metal, so that the ion balance is balanced to allow anions to be introduced. By introducing an organic anion into the layered inorganic mineral in this state, a layered inorganic compound modified with an organic anion can also be used.

[0103] By modifying at least a portion of the layered inorganic mineral with an organic ion, the mineral has a suitable hydrophobicity, and the oil phase containing the toner composition and / or the toner composition precursor has a non-Newtonian viscosity, making it possible to deform the toner.

[0104] Examples of layered inorganic minerals modified with organic cations include montmorillonite or bentonite, beidellite, nontronite, saponite, hectorite, attapulgite, sepiolite, and mixtures thereof. Among these, organically modified montmorillonite or bentonite is preferred because it does not affect the toner properties, allows easy viscosity adjustment, and allows the amount added to be small.

[0105] The organic cation modifier of the modified layered inorganic mineral may be a quaternary alkyl ammonium salt, a phosphonium salt, an imidazolium salt, etc., and preferably a quaternary alkyl ammonium salt. Examples of the quaternary alkyl ammonium include trimethylstearyl ammonium, dimethylstearylbenzyl ammonium, dimethyloctadecyl ammonium, and oleylbis(2-hydroxyethyl)methyl ammonium.

[0106] Examples of the modified layered inorganic minerals include BENTONE34, BENTONE52, BENTONE38, BENTONE27, BENTONE57, BENTONE SD1, BENTONE SD2, and BENTONE SD3 manufactured by ELEMENTIS Co., Ltd.; CRAYTONE34, CRAYTONE40, CRAYTONE HT, CRAYTONE2000, CRAYTONE AF, CRAYTONE APA, and CRAYTONE HY manufactured by SCP Co., Ltd.; Sben, Sben E, Sben C, Sben NZ, Sben NZ70, Sben W, Sben N400, Sben NX, Sben NX80, Sben NO12S, Sben NEZ, Sben NO12, Sben WX, and Sben NE manufactured by HOJUN Co., Ltd.; and KUNIVIS110, KUNIVIS120, and KUNIVIS127 manufactured by Kunimine Kogyo Co., Ltd.

[0107] The kneaded composite of the modified layered inorganic mineral and the binder resin, i.e., the master batch, can be obtained by mixing and kneading the binder resin and the modified layered inorganic mineral with high shear force. In this case, an organic solvent can be used to enhance the interaction between the modified layered inorganic mineral and the binder resin. In addition, a method called the so-called flushing method, in which an aqueous paste containing the modified layered inorganic mineral and water is mixed and kneaded with a resin and an organic solvent, the modified layered inorganic mineral is transferred to the resin side, and the water and organic solvent components are removed, is also preferably used because the wet cake can be used as it is and does not need to be dried. A high shear dispersing device such as a three-roll mill is preferably used for mixing and kneading.

[0108] In the kneaded composite of the modified layered inorganic mineral and the binder resin, i.e., in the master batch, it is desirable that the average dispersed particle size of the modified layered inorganic mineral is 0.1 μm or more and 0.55 μm or less, and the frequency of the modified layered inorganic mineral having a volume average particle size of 1 μm or more is 15% or less. If the average dispersed particle size exceeds 0.55 μm or the frequency of particles having a particle size of 1 μm or more exceeds 15%, the effect on the toner shape and the toner charging performance tends to decrease.

[0109] -External additives- The external additive is not particularly limited and can be appropriately selected according to the purpose, but includes at least silica. Examples of the external additive include various inorganic fine particles and hydrophobized inorganic fine particles. In addition, fatty acid metal salts (e.g., zinc stearate, aluminum stearate, etc.) and fluoropolymers can also be used.

[0110] Examples of the inorganic fine particles include silica, alumina, titanium oxide, barium titanate, magnesium titanate, calcium titanate, strontium titanate, iron oxide, copper oxide, zinc oxide, tin oxide, silica sand, clay, mica, wollastonite, diatomaceous earth, chromium oxide, cerium oxide, pengallo, antimony trioxide, magnesium oxide, zirconium oxide, barium sulfate, barium carbonate, calcium carbonate, silicon carbide, silicon nitride, etc. Among these, silica and titanium oxide are particularly preferred.

[0111] Suitable additives include hydrophobized silica, titania, titanium oxide, and alumina fine particles. Examples of silica fine particles include R972, R974, RX200, RY200, R202, R805, and R812 (all manufactured by Nippon Aerosil Co., Ltd.). Examples of titania fine particles include P-25 (manufactured by Nippon Aerosil Co., Ltd.), STT-30, and STT-65C-S (all manufactured by Titanium Industries Co., Ltd.), TAF-140 (manufactured by Fuji Titanium Industries Co., Ltd.), MT-150W, MT-500B, MT-600B, and MT-150A (all manufactured by Teika Co., Ltd.).

[0112] Examples of hydrophobically treated titanium oxide particles include T-805 (manufactured by Nippon Aerosil Co., Ltd.), STT-30A, STT-65S-S (all manufactured by Titanium Kogyo Co., Ltd.), TAF-500T, TAF-1500T (all manufactured by Fuji Titanium Kogyo Co., Ltd.), MT-100S, MT-100T (all manufactured by Teika Co., Ltd.), and IT-S (manufactured by Ishihara Sangyo Kaisha, Ltd.).

[0113] Hydrophobized oxide particles, hydrophobized silica particles, hydrophobized titania particles, and hydrophobized alumina particles can be obtained by treating hydrophilic particles with a silane coupling agent such as methyltrimethoxysilane, methyltriethoxysilane, octyltrimethoxysilane, etc. Silicone oil-treated oxide particles and inorganic particles, which are treated with silicone oil by heating as necessary, are also suitable.

[0114] Examples of the silicone oil include dimethyl silicone oil, methylphenyl silicone oil, chlorophenyl silicone oil, methylhydrogen silicone oil, alkyl-modified silicone oil, fluorine-modified silicone oil, polyether-modified silicone oil, alcohol-modified silicone oil, amino-modified silicone oil, epoxy-modified silicone oil, epoxy-polyether-modified silicone oil, phenol-modified silicone oil, carboxyl-modified silicone oil, mercapto-modified silicone oil, methacryl-modified silicone oil, and α-methylstyrene-modified silicone oil.

[0115] The average particle size of the primary particles of the inorganic fine particles is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 100 nm or less, more preferably 3 nm to 70 nm. If it is smaller than 3 nm, the inorganic fine particles are embedded in the toner and their function is not effectively exerted. If it is larger than 100 nm, it is not preferable because it will damage the photoreceptor surface unevenly.

[0116] The average particle size of the primary particles of the hydrophobized inorganic fine particles is preferably 1 nm to 100 nm, more preferably 5 nm to 70 nm. It is also preferable that the hydrophobized inorganic fine particles contain at least one type of inorganic fine particles having an average particle size of 20 nm or less, and at least one type of inorganic fine particles having an average particle size of 30 nm or more. The specific surface area by the BET method is 20 m 2 / g or more 500m 2 It is preferable that the molecular weight is not more than 1 / g. The content of the external additive is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.1 parts by mass to 5 parts by mass, more preferably 0.3 parts by mass to 3 parts by mass, relative to 100 parts by mass of the toner.

[0117] -Flow improver- The flowability improver is not particularly limited as long as it can improve hydrophobicity by surface treatment and prevent deterioration of flowability and charging property even under high humidity, and can be appropriately selected according to purpose.Examples thereof include silane coupling agent, silylating agent, silane coupling agent with fluorinated alkyl group, organic titanate coupling agent, aluminum coupling agent, silicone oil, modified silicone oil, etc.The silica and titanium oxide are particularly preferably surface-treated with such flowability improver and used as hydrophobic silica and hydrophobic titanium oxide.

[0118] -Cleaning improver- The cleaning property improver is added to the toner to remove the developer remaining on the photoconductor or the primary transfer medium after transfer, and is not particularly limited and can be appropriately selected according to the purpose. Examples include zinc stearate, calcium stearate, fatty acid metal salts such as stearic acid, polymethyl methacrylate fine particles, polystyrene fine particles, and other polymer fine particles produced by soap-free emulsion polymerization. The polymer fine particles preferably have a relatively narrow particle size distribution, and are preferably 0.01 μm or more and 1 μm or less in volume average particle size.

[0119] -Magnetic materials- The magnetic material is not particularly limited and may be appropriately selected depending on the purpose, and examples thereof include iron powder, magnetite, ferrite, etc. Among these, those that are white in color are preferred.

[0120] <Glass transition temperature (Tg1st)> The glass transition temperature (Tg1st) of the toner of the present invention at the first temperature rise in differential scanning calorimetry (DSC) is 45° C. or more and 65° C. or less, and preferably 50° C. or more and 60° C. or less. If the Tg is less than 45° C., the toner is likely to aggregate due to temperature changes during transportation and storage of the toner in summer or tropical regions. As a result, solidification in the toner bottle and toner adhesion in the developing machine occur. In addition, poor supply due to toner clogging in the toner bottle and image abnormalities due to toner adhesion in the developing machine tend to occur. If the Tg is greater than 65° C., good low-temperature fixability cannot be obtained.

[0121] The glass transition temperature (Tg1st) during the first temperature rise in DSC of the toner of the present invention can be adjusted to a desired range by changing the composition ratio of the aliphatic diol and the dicarboxylic acid component of polyester resin A, the glass transition temperature of polyester resin B, the glass transition temperature of polyester resin C, or the composition ratio of polyester resin A, polyester resin B and polyester resin C.

[0122] <Volume average particle size> The volume average particle diameter of the toner of the present invention is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 3 μm to 7 μm. The ratio of the volume average particle diameter to the number average particle diameter is preferably 1.2 or less. It is also preferable that the toner contains 1 number % to 10 number % of components having a volume average particle diameter of 2 μm or less.

[0123] <Silica release rate> The silica liberation rate of the toner of the present invention is preferably 0.20% by mass or more and less than 0.55% by mass, and more preferably 0.30% by mass or more and less than 0.45% by mass. If it is less than 0.20% by mass, the silica is easily embedded in the toner, which makes the belt cleaning property easily deteriorated, and if it is 0.55% by mass or more, the external additive is easily separated from the toner, which may contaminate the belt or photoreceptor and cause an abnormal image in the shape of a killifish. The silica liberation rate in the present invention refers to a value obtained using the ultrasonic vibration method described below.

[0124] <Silica release rate measurement using ultrasonic vibration method> 20g of carrier and 10g of toner are placed in a 50mL vial. This is set in a rocking mill (RM-05, manufactured by Seiwa Giken Co., Ltd.), and the toner and carrier are mixed under the conditions of 67Hz / 60min, and then the carrier and toner are separated. There is no particular restriction on the carrier and it can be appropriately selected depending on the purpose, but it is preferable to use a carrier having a core material and a resin layer that covers the core material. There is no particular restriction on the method for separating the carrier and toner, but the toner and carrier can be separated by transferring the mixed toner and carrier to any container, placing a neodymium magnet on the back side of the container, and vibrating it. In a 500 mL beaker, 10 g of polyoxyalkylene alkyl ether (Noigen ET-165, Daiichi Kogyo Seiyaku Co., Ltd.) and 300 mL of pure water were placed, and dispersed by ultrasonication for 1 hour to obtain Dispersion A. Dispersion A was then transferred to a 2 L measuring flask, diluted with the solution, and dissolved by ultrasonication for 1 hour to obtain Dispersion B containing 0.5% polyoxyalkylene alkyl ether.

[0125] 50 mL of dispersion B was poured into a 110 mL screw tube, and 3.75 g of the toner sample separated as above was added. Dispersion C was obtained by stirring for 30 to 90 minutes until the screw tube was acclimated to dispersion B. At this time, the rotation was kept as low as possible to prevent bubbles from being generated. After the toner was sufficiently dispersed, the vibration part of an ultrasonic homogenizer (VCX750, manufactured by SONICS & Materials, Inc., 20 kHz, 750 watts) was inserted 2.5 cm into dispersion C, and ultrasonic vibration was applied for 1 minute at an output energy of 40%, to produce dispersion D.

[0126] Dispersion D was placed in a 50 mL centrifuge tube and centrifuged at 2,000 rpm for 2 minutes to obtain a supernatant and a precipitate. The precipitate was poured into a separatory funnel while being washed with 60 mL of pure water, and the washing water was removed by suction filtration. The precipitate after filtration was placed again in a mini cup, 60 mL of pure water was poured into the mini cup, and the mixture was stirred five times with the handle of a spatula. Do not stir too vigorously at this time. The washing water was removed again by suction filtration, and the toner remaining on the filter paper was collected and dried for 8 hours in a 40°C thermostatic chamber. 3 g of the toner obtained after drying was pelletized to a diameter of 3 mm and a thickness of 2 mm using an automatic pressure molding machine (T-BRB-32, Maekawa Co., Ltd.; load 6.0 t, pressure time 60 seconds), and used as a sample toner after processing. The initial sample toner that had not been subjected to the above treatment was similarly molded into pellets having a diameter of 3 mm and a thickness of 2 mm to prepare pre-treatment sample toner.

[0127] The amount of silica in the pelletized sample toner was measured by quantitative analysis using a fluorescent X-ray analyzer (ZSX-100e, manufactured by Rigaku Corporation). The calibration curve was prepared in advance using sample toners with silica contents of 0.1, 1, and 1.8 parts per 100 parts of toner.

[0128] The silica liberation rate (mass%) was calculated by the following formula. Silica liberation rate A (mass%)=[Silica content of sample toner before treatment (parts)−Silica content of sample toner after treatment (parts)] / sample toner before treatment (parts)×100

[0129] <Methods of calculating and analyzing various characteristics of toner and toner components> Next, the calculation method and analysis method of various properties of the toner and toner components will be described. The glass transition temperature Tg, acid value, hydroxyl value, molecular weight, and melting point of the toner components such as the polyester resins A, B, and C, the crystalline polyester resin, and the release agent may be measured for each of them, or may be measured for each of the separated components by separating them from the actual toner using Soxhlet extraction or gel permeation chromatography (GPC). In the present invention, the means for separating the toner components in the toner can be selected arbitrarily, but the glass transition temperature Tg of the target sample is measured by the method described below.

[0130] First, an example will be described. An example of a method for measuring the glass transition temperature of each of polyester resin A, polyester resin B, and polyester resin C in a toner will be shown. 1 g of toner is placed in 100 mL of THF, and Soxhlet extraction is performed to obtain a THF-soluble fraction and an insoluble fraction. This is then dried for 24 hours in a vacuum dryer, and a mixture of polyester resin C and crystalline polyester resin is obtained from the THF-soluble fraction, and a mixture of polyester resin A and polyester resin B is obtained from the THF-insoluble fraction. These are used as target samples, and the glass transition temperatures are measured using the method described below.

[0131] In addition, since polyester resin A and polyester resin B have different glass transition temperatures, the glass transition temperatures of polyester resin A and polyester resin B can be determined by obtaining a mixture of polyester resin A and polyester resin B as described above and measuring the glass transition temperature of this mixture.

[0132] Next, other examples will be described. 1 g of toner is put into 100 mL of THF, and the solution is obtained by stirring for 30 minutes under a condition of 25°C, in which the soluble portion is dissolved. This is filtered through a membrane filter with an opening of 0.2 μm to obtain the THF-soluble portion in the toner. Next, this is dissolved in THF to prepare a sample for GPC measurement, and is injected into a GPC used to measure the molecular weight of polyester resin C. In addition, the THF-insoluble portion in the toner is used as a sample for GPC measurement as a sample for measurement of polyester resin A and polyester resin B. On the other hand, a fraction collector is placed at the eluate outlet of the GPC, and the eluate is collected at every predetermined count, and the eluate is obtained at every 5% area ratio from the start of elution (the rise of the curve) of the elution curve. Next, for each elution, 30 mg of sample is dissolved in 1 mL of deuterated chloroform, and 0.05 vol% of tetramethylsilane (TMS) is added as a reference substance. The solution is filled into a 5 mm diameter glass tube for NMR measurement, and a nuclear magnetic resonance device (JNM-AL400 manufactured by JEOL Ltd.) is used to perform 128 integrations at 23°C to 25°C to obtain a spectrum. The monomer composition and composition ratio of polyester resins A, B, C, crystalline polyester resin, etc. contained in the toner can be obtained from the peak integral ratio of the obtained spectrum.

[0133] Next, an example of separation of each component by GPC will be described. In GPC measurement using THF as the mobile phase, the eluate is fractionated using a fraction collector or the like, and fractions corresponding to the desired molecular weight portion of the full integral of the elution curve are collected. Next, the collected eluate is concentrated and dried using an evaporator or the like, and the solid content is dissolved in a heavy solvent such as deuterated chloroform or deuterated THF, and 1H-NMR measurement is performed to calculate the constituent monomer ratio of the resin in the eluted component from the integral ratio of each element. As another method, the eluate may be concentrated, hydrolyzed with sodium hydroxide or the like, and the decomposition product may be qualitatively and quantitatively analyzed by high performance liquid chromatography (HPLC) or the like to calculate the constituent monomer ratio.

[0134] In addition, in the case where the toner manufacturing method forms toner base particles while generating a polyester resin by an elongation reaction and / or a crosslinking reaction between a non-linear reactive precursor and a curing agent, the polyester resin may be separated from the actual toner by GPC or the like to determine the Tg and other properties of the polyester resin, or a polyester resin may be synthesized separately by an elongation reaction and / or a crosslinking reaction between a non-linear reactive precursor and a curing agent, and the Tg and other properties of the synthesized polyester resin may be measured.

[0135] <<Measuring method for melting point and glass transition temperature Tg>> The melting point and glass transition temperature Tg in the present invention are measured using a DSC system (differential scanning calorimeter) ("Q-200", manufactured by TA Instruments). Specifically, the melting point and glass transition temperature of the sample are measured according to the following procedure. First, about 5.0 mg of the target sample is placed in an aluminum sample container, the sample container is placed on a holder unit, and set in an electric furnace. Next, in a nitrogen atmosphere, the sample is heated from -80°C to 150°C at a heating rate of 10°C / min (first heating). After that, the sample is cooled from 150°C to -80°C at a heating rate of 10°C / min, and further heated to 150°C at a heating rate of 10°C / min (second heating). During each of the first and second heating, a DSC curve is measured using a differential scanning calorimeter ("Q-200", manufactured by TA Instruments).

[0136] From the obtained DSC curves, the DSC curve at the first temperature rise can be selected using the analysis program in the Q-200 system, and the glass transition temperature at the first temperature rise of the target sample can be obtained. Similarly, the DSC curve at the second temperature rise can be selected, and the glass transition temperature at the second temperature rise of the target sample can be obtained.

[0137] In the present invention, the obtained DSC curve is analyzed using an analysis program in the Q-200 system, with "Reversing Heat Flow" plotted on the vertical axis to obtain a DSC curve as shown in FIG. 1, and the onset value shown in FIG. 1 is taken as the Tg in the present invention.

[0138] In addition, this measurement is preferably performed by raising the temperature by applying a modulation temperature amplitude as shown below, since the glass transition temperature (Tga1st and Tgb1st) of the first temperature rise can be separated into two points in the THF-insoluble components of the toner.

[0139] (Measurement conditions) Using the modulation mode, heat from -80°C to 150°C at a heating rate of 1.0°C / min with a modulation temperature amplitude of ±1.0°C / min (first heating), then cool from 150°C to -80°C at a temperature drop rate of 10°C / min, and further heat to 150°C at a heating rate of 1.0°C / min (second heating). The obtained DSC curve is analyzed using the analysis program in the Q-200 system in the same manner as above, with "Reversing Heat Flow" plotted on the vertical axis to obtain a DSC curve, and the onset value is taken as Tg.

[0140] Furthermore, from the obtained DSC curves, the analysis program in the Q-200 system can be used to select the DSC curve during the first heating and determine the endothermic peak top temperature during the first heating of the target sample as the melting point. Similarly, the DSC curve during the second heating can be selected and the endothermic peak top temperature during the second heating of the target sample as the melting point.

[0141] Unless otherwise specified, the melting points and glass transition temperatures Tg of the polyester resins A, B, and C, the release agent, and other constituent components are the endothermic peak top temperature and glass transition temperature Tg2nd during the second heating, respectively, of each sample.

[0142] <Mass ratio of polyester resin> In the present invention, when the mass ratio of polyester resin A to the total mass of polyester resin A, polyester resin B, and polyester resin C is a, the mass ratio of polyester resin B is b, and the mass ratio of polyester resin C is c, 4(a+b) <c In this case, separation of the resin can be prevented, and poor dispersion of the pigment and a decrease in coloring degree can be prevented. In addition, a good image can be obtained, and fixing area and storage stability can be ensured.

[0143] In this embodiment, as described above, the mass ratio of the polyester resins can be determined by obtaining the combined product of polyester resins A and B, and the combined product of polyester resin C and the crystalline polyester resin in the toner by Soxhlet extraction, GPC, or the like, and then calculating the masses thereof.

[0144] <Toner manufacturing method> The method for producing the toner is not particularly limited and can be appropriately selected depending on the purpose. However, it is preferable to granulate the toner by dispersing an oil phase containing the polyester resins A, B, and C and, if necessary, the crystalline polyester resin, a release agent, a colorant, etc., in an aqueous medium. The polyester resins A and B are a polyester resin which is a prepolymer having a urethane bond and / or a urea bond, and a polyester resin which is a urethane bond and / or a urea bond. It is more preferable that the granulation is carried out by dispersing an oil phase containing a polyester resin that does not contain a crystalline polyester resin, preferably the crystalline polyester resin, and further containing, as necessary, the curing agent, the releasing agent, the colorant, etc., in an aqueous medium.

[0145] As a method for producing such a toner, a known solution suspension method can be mentioned. As an example, a method of forming toner base particles while generating a polyester resin by an elongation reaction and / or a crosslinking reaction between the prepolymer and the curing agent will be described. In this method, an aqueous medium is prepared, an oil phase containing the toner materials is prepared, the toner materials are emulsified or dispersed, and the organic solvent is removed.

[0146] - Preparation of aqueous medium (aqueous phase) - The aqueous medium can be prepared, for example, by dispersing resin particles in the aqueous medium. The amount of the resin particles added to the aqueous medium is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the aqueous medium. The aqueous medium is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include water, a solvent miscible with water, and a mixture thereof. These may be used alone or in combination of two or more. Among these, water is preferred.

[0147] The water-miscible solvent is not particularly limited and may be appropriately selected depending on the purpose. Examples of the alcohol include alcohol, dimethylformamide, tetrahydrofuran, cellosolves, lower ketones, etc. Examples of the alcohol include methanol, isopropanol, ethylene glycol, etc. Examples of the lower ketones include acetone, methyl ethyl ketone, etc.

[0148] - Preparation of oil phase - In the present embodiment, the oil phase containing the toner materials can be prepared by dissolving or dispersing toner materials including polyester resins A and B, which are prepolymers having a urethane bond and / or a urea bond, and polyester resin C having no urethane bond and / or urea bond, and further including the crystalline polyester resin, a curing agent, a releasing agent, a colorant, and the like, as necessary, in an organic solvent.

[0149] The organic solvent is not particularly limited and can be appropriately selected depending on the purpose, but an organic solvent having a boiling point of less than 150° C. is preferred in terms of ease of removal.

[0150] Examples of the organic solvent having a boiling point of less than 150° C. include toluene, xylene, benzene, carbon tetrachloride, methylene chloride, 1,2-dichloroethane, 1,1,2-trichloroethane, trichloroethylene, chloroform, monochlorobenzene, dichloroethylidene, methyl acetate, ethyl acetate, methyl ethyl ketone, and methyl isobutyl ketone. These may be used alone or in combination of two or more. Among these, ethyl acetate, toluene, xylene, benzene, methylene chloride, 1,2-dichloroethane, chloroform, carbon tetrachloride, etc. are preferable, and ethyl acetate is more preferable.

[0151] -Emulsification or dispersion- The toner materials can be emulsified or dispersed by dispersing an oil phase containing the toner materials in the aqueous medium, and when the toner materials are emulsified or dispersed, the curing agent and the prepolymer can undergo an elongation reaction and / or a crosslinking reaction.

[0152] The reaction conditions (reaction time, reaction temperature) for producing the prepolymer are not particularly limited and can be appropriately selected depending on the combination of the curing agent and the prepolymer. The reaction time is preferably 10 minutes to 40 hours, more preferably 2 hours to 24 hours. The reaction temperature is preferably 0°C to 150°C, more preferably 40°C to 98°C.

[0153] The step of uniformly dispersing the oil phase is not particularly limited, and a homomixer, a milder, or a bead mill can be appropriately selected depending on the oil phase formulation, the viscosity of the oil phase, etc. The dispersion time is preferably 1 hour to 5 hours, and more preferably 1 hour to 3 hours.

[0154] The method for stably forming a dispersion liquid containing the prepolymer in the aqueous medium is not particularly limited and can be appropriately selected depending on the purpose. For example, there is a method in which an oil phase prepared by dissolving or dispersing a toner material in a solvent is added to an aqueous medium phase, and the mixture is dispersed by shear force.

[0155] The dispersing machine for the dispersion is not particularly limited and can be appropriately selected according to the purpose. For example, low-speed shear dispersing machine, high-speed shear dispersing machine, friction dispersing machine, high-pressure jet dispersing machine, ultrasonic dispersing machine, etc. can be mentioned. Among these, high-speed shear dispersing machine is preferable because it can control the particle size of the dispersion (oil droplets) to 2 μm to 20 μm.

[0156] When using the high-speed shear type disperser, the conditions such as the rotation speed, dispersion time, and dispersion temperature can be appropriately selected depending on the purpose. The rotation speed is preferably 1,000 rpm to 30,000 rpm, and more preferably 5,000 rpm to 20,000 rpm. In the case of a batch method, the dispersion time is preferably 0.1 minutes to 5 minutes. The dispersion temperature is preferably 0°C to 150°C under pressure, and more preferably 40°C to 98°C. Generally, the higher the dispersion temperature, the easier the dispersion.

[0157] The amount of the aqueous medium used when emulsifying or dispersing the toner materials is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 50 parts by mass or more and 2,000 parts by mass or less, and more preferably 100 parts by mass or more and 1,000 parts by mass or less, relative to 100 parts by mass of the toner materials. By using an aqueous medium of 50 parts by mass or more, the dispersion state of the toner materials becomes good, and toner base particles of a predetermined particle size can be obtained. In addition, by using an aqueous medium of 2,000 parts by mass or less, the production cost does not increase.

[0158] When the oil phase containing the toner materials is emulsified or dispersed, it is preferable to use a dispersant from the viewpoints of stabilizing the dispersion such as oil droplets, forming a desired shape, and sharpening the particle size distribution. The dispersant is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include surfactants, poorly water-soluble inorganic compound dispersants, polymer-based protective colloids, etc. These may be used alone or in combination of two or more. Among these, surfactants are preferred.

[0159] The surfactant is not particularly limited and can be appropriately selected according to the purpose. For example, anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, etc. can be used. Examples of the anionic surfactant include alkylbenzene sulfonates, α-olefin sulfonates, and phosphate esters. Among these, those having a fluoroalkyl group are preferred. The amount of the surfactant added in the aqueous medium is not particularly limited and can be appropriately selected according to the purpose, but is preferably 1.0 parts by mass or more and 10 parts by mass or less, more preferably 1.0 parts by mass or more and 6.5 parts by mass or less, and even more preferably 1.0 parts by mass or more and 3.5 parts by mass or less, relative to 100 parts by mass of the aqueous medium.

[0160] -Removal of organic solvents- The method for removing the organic solvent from the dispersion liquid such as the emulsified slurry is not particularly limited and can be appropriately selected depending on the purpose. Examples of the method include a method in which the temperature of the entire reaction system is gradually increased to evaporate the organic solvent in the oil droplets, and a method in which the dispersion liquid is sprayed in a dry atmosphere to remove the organic solvent in the oil droplets. When the organic solvent is removed, toner base particles are formed. The toner base particles can be washed, dried, and further classified. For the washing step, hot water may be used, and the temperature is preferably 50°C to 55°C. The classification may be performed by removing fine particles in a liquid using a cyclone, decanter, or centrifugal separation, or the classification operation may be performed after drying.

[0161] The obtained toner base particles may be mixed with particles of the external additive, the charge control agent, etc. At this time, by applying a mechanical impact force, it is possible to suppress the particles of the external additive, etc. from being detached from the surface of the toner base particles. The method of applying the mechanical impact force is not particularly limited and can be appropriately selected depending on the purpose. Examples of the method include a method of applying an impact force to the mixture using a blade rotating at high speed, a method of introducing the mixture into a high-speed air stream and accelerating it to collide the particles with each other or with a suitable collision plate, etc.

[0162] There is no particular limitation on the apparatus used in the above method, and it can be appropriately selected depending on the purpose. Examples include the Ang Mill (manufactured by Hosokawa Micron Corporation), a modified I-type Mill (manufactured by Japan Pneumatic Co., Ltd.) with reduced grinding air pressure, the Hybridization System (manufactured by Nara Machinery Works), the Cryptron System (manufactured by Kawasaki Heavy Industries, Ltd.), and the automatic mortar.

[0163] (Developer) The developer of the present invention contains at least the toner of the present invention, and contains other components such as a carrier, which are appropriately selected as necessary. Therefore, it has excellent transferability, chargeability, etc., and can stably form high-quality images. The developer may be a one-component developer or a two-component developer, but when used in a high-speed printer that corresponds to the recent improvement in information processing speed, a two-component developer is preferred because it has an improved life.

[0164] When the developer is used as a one-component developer, even if the toner is balanced, there is little variation in the particle size of the toner, there is little filming of external additives onto the developing roller, and there is little fusion of the toner to components such as blades that thin the toner layer, and good and stable developability and images can be obtained even with long-term stirring in the developing device.

[0165] When the developer is used as a two-component developer, even if the toner is balanced over a long period of time, the particle size of the toner does not vary much, and good and stable developability and images can be obtained even with long-term stirring in a developing device.

[0166] <Career> The carrier is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable that the carrier has a core material and a resin layer that covers the core material.

[0167] -Core material- The material of the core material is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include manganese-strontium-based materials of 50 emu / g to 90 emu / g and manganese-magnesium-based materials of 50 emu / g to 90 emu / g. In order to ensure image density, it is preferable to use high magnetization materials such as iron powder of 100 emu / g or more and magnetite of 75 emu / g to 120 emu / g. In addition, it is preferable to use low magnetization materials such as copper-zinc-based materials of 30 to 80 emu / g, since it can reduce the impact of the developer in a standing state on the photoconductor and is advantageous for improving image quality. These may be used alone or in combination of two or more.

[0168] The volume average particle diameter of the core material is not particularly limited and can be appropriately selected according to the purpose, but is preferably 10 μm to 150 μm, more preferably 40 μm to 100 μm. If the volume average particle diameter is less than 10 μm, the amount of fine powder in the carrier increases, the magnetization per particle decreases, and the carrier may scatter. On the other hand, if it exceeds 150 μm, the specific surface area decreases, the toner may scatter, and in full color with many solid parts, the reproduction of the solid parts may be particularly poor.

[0169] The toner of the present invention can be mixed with the above-mentioned carrier and used in a two-component developer. The content of the carrier in the two-component developer is not particularly limited and can be appropriately selected depending on the purpose. However, the content is preferably 90 parts by mass or more and 98 parts by mass or less, and more preferably 93 parts by mass or more and 97 parts by mass or less, relative to 100 parts by mass of the two-component developer. The developer of the present invention can be suitably used for image formation by various known electrophotographic methods such as a magnetic one-component development method, a non-magnetic one-component development method, and a two-component development method.

[0170] (Developer container) The developer container for housing the developer of the present invention is not particularly limited and can be appropriately selected from known containers. For example, a container having a container body and a cap can be used. The size, shape, structure, material, etc. of the container body are not particularly limited, but the shape is preferably cylindrical or the like. In particular, a spiral unevenness is formed on the inner peripheral surface, and the developer, which is the content, can be moved to the discharge port side by rotating, and it is preferable that a part or all of the spiral unevenness has a bellows function. In addition, the material is preferably one with good dimensional accuracy. Examples of such materials include resin materials such as polyester resin, polyethylene resin, polypropylene resin, polystyrene resin, polyvinyl chloride resin, polyacrylic acid, polycarbonate resin component ABS resin, and polyacetal resin.

[0171] The developer storage container is easy to store, transport, and the like, and has excellent handleability, and therefore can be detachably attached to a process cartridge, an image forming apparatus, and the like, which will be described later, and used for replenishing the developer.

[0172] (Image forming apparatus and image forming method) The image forming apparatus of the present invention comprises at least an electrostatic latent image carrier, an electrostatic latent image forming means, and a developing means, and further comprises other means as necessary. The image forming method according to the present invention includes at least an electrostatic latent image forming step and a development step, and further includes other steps as necessary.

[0173] <Electrostatic latent image carrier> The material, structure, and size of the electrostatic latent image bearing member are not particularly limited and may be appropriately selected from known materials, and examples of the material include inorganic photoconductors such as amorphous silicon and selenium, and organic photoconductors such as polysilane and phthalopolymethine, etc. Among these, amorphous silicon is preferred in terms of long life. The linear speed of the electrostatic latent image bearing member is preferably 300 mm / s or more.

[0174] <Electrostatic latent image forming means and electrostatic latent image forming process> The electrostatic latent image forming means is not particularly limited as long as it is a means for forming an electrostatic latent image on the electrostatic latent image carrier, and may be appropriately selected depending on the purpose. For example, there may be mentioned a means having at least a charging member that charges the surface of the electrostatic latent image carrier, and an exposure member that exposes the surface of the electrostatic latent image carrier to light in an imagewise manner.

[0175] The electrostatic latent image forming step is not particularly limited as long as it is a step of forming an electrostatic latent image on the electrostatic latent image bearing member, and can be appropriately selected depending on the purpose. For example, the electrostatic latent image forming step can be performed by charging the surface of the electrostatic latent image bearing member and then exposing it to light in an imagewise manner, using the electrostatic latent image forming means.

[0176] <<Charging materials and charging>> The charging member is not particularly limited and can be appropriately selected depending on the purpose. Examples of the charging member include a contact charger known per se having a conductive or semiconductive roller, brush, film, rubber blade, or the like, and a non-contact charger utilizing corona discharge such as a corotron or scorotron.

[0177] The charging is performed, for example, by applying a voltage to the surface of the electrostatic latent image carrier using the charging member. This can be done by: The shape of the charging member may be any shape, such as a roller, a magnetic brush, a fur brush, etc., and can be selected according to the specifications and shape of the image forming apparatus.

[0178] The charging member is not limited to the contact-type charging member, but it is preferable to use a contact-type charging member because it allows an image forming apparatus in which the amount of ozone generated from the charging member is reduced.

[0179] <<Exposure materials and exposure>> The exposing member is not particularly limited and may be appropriately selected depending on the purpose as long as it can expose the surface of the electrostatic latent image carrier charged by the charging member in the form of an image to be formed, and examples of the exposing member include various exposing members such as a copying optical system, a rod lens array system, a laser optical system, and a liquid crystal shutter optical system.

[0180] The light source used in the exposure member is not particularly limited and can be appropriately selected depending on the purpose. For example, fluorescent lamps, tungsten lamps, halogen lamps, mercury lamps, sodium lamps, light-emitting diodes (LEDs), semiconductor lasers (LDs), electroluminescence (EL), and other light-emitting materials in general can be mentioned.

[0181] In order to irradiate only light in a desired wavelength range, various filters such as a sharp cut filter, a band pass filter, a near infrared cut filter, a dichroic filter, an interference filter, and a color temperature conversion filter can be used.

[0182] The exposure can be carried out, for example, by exposing the surface of the electrostatic latent image bearing member imagewise using the exposure member. In the present invention, a light back system may be adopted in which exposure is performed imagewise from the back side of the electrostatic latent image bearing member.

[0183] <Developing means and developing process> The developing unit is not particularly limited as long as it is a developing unit that develops the electrostatic latent image formed on the electrostatic latent image carrier to form a toner image, which is a visible image, and is equipped with a toner, and can be appropriately selected depending on the purpose. The developing step is not particularly limited as long as it is a step of developing the electrostatic latent image formed on the electrostatic latent image carrier with a toner to form a toner image, which is a visible image, and can be appropriately selected depending on the purpose. For example, the developing step can be performed by the developing means. The developing means is preferably a developing device having an agitator that frictionally agitates the toner to charge it, a magnetic field generating means fixed inside, and a developer carrier that can rotate and carries a developer containing the toner on its surface.

[0184] <Other means and other steps> Examples of the other means include a transfer means, a fixing means, a cleaning means, a discharging means, a recycling means, and a control means. Examples of the other steps include a transfer step, a fixing step, a cleaning step, a discharging step, a recycling step, and a control step.

[0185] <<Transfer means and transfer process>> The transfer means is not particularly limited as long as it is a means for transferring a visible image onto a recording medium, and can be appropriately selected depending on the purpose. However, a preferred embodiment has a primary transfer means for transferring the visible image onto an intermediate transfer body to form a composite transfer image, and a secondary transfer means for transferring the composite transfer image onto a recording medium. The transfer step is not particularly limited as long as it is a step of transferring a visible image onto a recording medium, and may be appropriately selected depending on the purpose. However, a preferred embodiment is one in which an intermediate transfer body is used, a visible image is primarily transferred onto the intermediate transfer body, and then the visible image is secondarily transferred onto the recording medium. The transfer step can be carried out by, for example, charging the visible image on the photoconductor using a transfer charger, and can be carried out by the transfer unit.

[0186] Here, when the image to be secondarily transferred onto the recording medium is a color image made up of toners of multiple colors, the transfer means can be configured to sequentially overlay toners of each color on the intermediate transfer body to form an image on the intermediate transfer body, and the intermediate transfer means can be configured to secondarily transfer the image on the intermediate transfer body onto the recording medium all at once. The intermediate transfer body is not particularly limited and can be appropriately selected from known transfer bodies depending on the purpose. For example, a transfer belt is preferably used.

[0187] The transfer means (the primary transfer means and the secondary transfer means) preferably has at least a transfer device that peels and charges the visible image formed on the photoreceptor onto the recording medium. Examples of the transfer device include a corona transfer device that uses corona discharge, a transfer belt, a transfer roller, a pressure transfer roller, and an adhesive transfer device. The recording medium is typically plain paper, but is not particularly limited as long as it is capable of transferring an unfixed image after development, and can be appropriately selected according to the purpose. A PET base for overhead projectors can also be used.

[0188] <<Fixing means and fixing process>> The fixing means is not particularly limited as long as it is a means for fixing the transferred image transferred to the recording medium, and can be appropriately selected according to the purpose. For example, a known heating and pressing member is preferable. Examples of the heating and pressing member include a combination of a heating roller and a pressing roller, and a combination of a heating roller, a pressing roller, and an endless belt. The fixing step is not particularly limited as long as it is a step of fixing the visible image transferred to the recording medium, and can be appropriately selected according to the purpose. For example, the fixing step may be performed for each color toner transferred to the recording medium, or may be performed simultaneously for each color toner in a laminated state.

[0189] The fixing step can be carried out by the fixing means. The heating temperature in the heating and pressing member is preferably 80°C to 200°C. In the present invention, depending on the purpose, for example, a known optical fixing device may be used together with or instead of the fixing means. The surface pressure in the fixing step is not particularly limited and can be appropriately selected depending on the purpose. 2 ~80N / cm 2 It is preferable that:

[0190] <<Cleaning means and cleaning process>> The cleaning means is not particularly limited as long as it can remove the toner remaining on the photoreceptor, and can be appropriately selected depending on the purpose, for example, a magnetic brush cleaner, an electrostatic brush cleaner, a magnetic roller cleaner, a blade cleaner, a brush cleaner, a web cleaner, etc. The cleaning step is not particularly limited as long as it can remove the toner remaining on the photoconductor, and can be appropriately selected depending on the purpose. For example, the cleaning step can be performed by the cleaning unit.

[0191] <<Static charge removal means and static charge removal process>> The charge removing means is not particularly limited as long as it is a means for removing electricity by applying a charge removing bias to the photoconductor, and may be appropriately selected depending on the purpose. For example, a charge removing lamp may be used. The charge removing step is not particularly limited as long as it is a step of removing electricity by applying a charge removing bias to the photoconductor, and may be appropriately selected depending on the purpose. For example, the charge removing step may be performed by the charge removing unit.

[0192] <<Recycling methods and processes>> The recycling means is not particularly limited as long as it is a means for recycling the toner removed in the cleaning step to the developing device, and can be appropriately selected depending on the purpose. For example, a known transport means can be used. The recycling process is not particularly limited as long as it is a process for recycling the toner removed by the cleaning process back into the developing device, and can be appropriately selected depending on the purpose. For example, the recycling process can be performed by the recycling means.

[0193] Next, one embodiment of a method for forming an image by the image forming apparatus of the present invention will be described with reference to Fig. 2. Although a printer is shown as an example of the image forming apparatus of this embodiment, the image forming apparatus is not particularly limited as long as it is capable of forming an image using toner, such as a copier, facsimile, or multifunction machine. The image forming apparatus includes a paper feed section 210, a conveying section 220, an image creating section 230, a transfer section 240, and a fixing unit 250. The paper feed section 210 includes a paper feed cassette 211 in which the paper P to be fed is stacked, and a paper feed roller 212 that feeds the paper P stacked in the paper feed cassette 211 one sheet at a time.

[0194] The conveying section 220 includes a roller 221 that conveys the paper P fed by the paper feed roller 212 toward the transfer section 240, a pair of timing rollers 222 that hold the leading end of the paper P conveyed by the roller 221 and wait to send the paper to the transfer section 240 at a predetermined timing, and a paper discharge roller 223 that discharges the paper P with the color toner image fixed thereto onto a paper discharge tray 224.

[0195] The image creating section 230 includes, spaced at a predetermined interval from left to right in the figure, an image forming unit Y that forms an image using a developer containing yellow toner, an image forming unit C that uses a developer containing cyan toner, an image forming unit M that uses a developer containing magenta toner, an image forming unit K that uses a developer containing black toner, and exposure devices (233Y, 233C, 233M, 233K). Incidentally, when referring to any one of the image forming units (Y, C, M, K), it is referred to as an image forming unit.

[0196] The developer contains toner and carrier. The four image forming units (Y, C, M, K) have substantially the same mechanical configuration, except for the developer used in each unit.

[0197] The transfer unit 240 includes a drive roller 241 and a driven roller 242, an intermediate transfer belt 243 that can rotate counterclockwise in the figure as the drive roller 241 is driven, primary transfer rollers (244Y, 244C, 244M, 244K) arranged opposite the photosensitive drums (231Y, 231C, 231M, 231K) across the intermediate transfer belt 243, and secondary opposing roller 245 and secondary transfer roller 246 arranged opposite each other across the intermediate transfer belt 243 at the transfer position of the toner image to paper.

[0198] The fixing unit 250 has a heater installed inside and is equipped with a pressure roller 252 that forms a nip by rotatably pressing a fixing belt 251, which heats the paper P, against the fixing belt 251. This applies heat and pressure to the color toner image on the paper P, fixing the color toner image. The paper P with the fixed color toner image is discharged to a paper discharge tray 224 by a paper discharge roller 223, completing a series of image formation processes.

[0199] (Toner storage unit) The toner storage unit in the present invention refers to a unit having a function of storing toner and storing the toner. Examples of the toner storage unit include a toner storage container, a developing unit, and a process cartridge. The toner storage container refers to a container that stores toner. The developing device has a means for containing toner and developing the toner.

[0200] The process cartridge is a cartridge that integrates at least an electrostatic latent image carrier (also called an image carrier) and a developing means, contains toner, and is detachable from an image forming apparatus. The process cartridge may further include at least one selected from a charging means, an exposure means, and a cleaning means. By mounting the toner storage unit of the present invention in an image forming apparatus and forming an image, it is possible to form a high-definition, high-quality image while ensuring the brilliance of the image.

[0201] (Process cartridge) The process cartridge according to the present invention is molded so as to be detachably mountable to various image forming apparatuses, and has at least an electrostatic latent image carrier for carrying an electrostatic latent image, and a developing means for developing the electrostatic latent image carried on the electrostatic latent image carrier with the developer of the present invention to form a toner image. The process cartridge of the present invention may further have other means as necessary.

[0202] The developing means includes at least a developer container that contains the developer of the present invention, and a developer carrier that carries and transports the developer contained in the developer container. The developing means may further include a regulating member or the like for regulating the thickness of the developer carried.

[0203] An example of a process cartridge according to the present invention is shown in Fig. 3. The process cartridge 110 has the photosensitive drum 10, a corona charger 58, a developing device 40, a transfer roller 80 and a cleaning device 90. EXAMPLES

[0204] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples. In the following, unless otherwise specified, "parts" means parts by mass and "%" means % by mass.

[0205] The "prepolymer" synthesized below is the raw material for the "polyester resin," and in the toner manufacturing process, the "prepolymer" becomes the "polyester resin," which exists in the toner as the "polyester resin." The mass ratios a, b, and c of the polyester resin described above are calculated by analyzing the toner, as described below.

[0206] (Manufacturing example A-1) <Synthesis of Prepolymer A-1> Into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 3-methyl-1,5-pentanediol, isophthalic acid, adipic acid, and trimellitic anhydride were added together with titanium tetraisopropoxide (1,000 ppm relative to the resin component) so that the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.5, the diol component was 100 mol% 3-methyl-1,5-pentanediol, the dicarboxylic acid component was 40 mol% isophthalic acid and 60 mol% adipic acid, and the amount of trimellitic anhydride in all monomers was 1 mol%. Thereafter, the temperature was raised to 200°C over about 4 hours, and then to 230°C over 2 hours, and the reaction was continued until no water was discharged. Thereafter, the mixture was further reacted for 5 hours under a reduced pressure of 10 mmHg to 15 mmHg to obtain [Intermediate Polyester A-1]. Next, [Intermediate polyester A-1] and isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, and after diluting with ethyl acetate to make a 50% ethyl acetate solution, the mixture was reacted at 100°C for 5 hours to obtain [Prepolymer A-1].

[0207] (Manufacturing example A-2) <Synthesis of prepolymer A-2> Into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 3-methyl-1,5-pentanediol, isophthalic acid, adipic acid, and trimellitic anhydride were added together with titanium tetraisopropoxide (1,000 ppm relative to the resin component) so that the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.5, the diol component was 100 mol% 3-methyl-1,5-pentanediol, the dicarboxylic acid component was 33 mol% isophthalic acid and 67 mol% adipic acid, and the amount of trimellitic anhydride in all monomers was 1 mol%. Thereafter, the temperature was raised to 200°C over about 4 hours, and then to 230°C over 2 hours, and the reaction was continued until no water was discharged. Thereafter, the mixture was further reacted for 5 hours under a reduced pressure of 10 mmHg to 15 mmHg to obtain [Intermediate Polyester A-2]. Next, [Intermediate polyester A-2] and isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, and after diluting with ethyl acetate to make a 50% ethyl acetate solution, the mixture was reacted at 100°C for 5 hours to obtain [Prepolymer A-2].

[0208] (Manufacturing example A-3) <Synthesis of prepolymer A-3> Into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 3-methyl-1,5-pentanediol, isophthalic acid, adipic acid, and trimellitic anhydride were added together with titanium tetraisopropoxide (1,000 ppm relative to the resin component) so that the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.5, the diol component was 100 mol% 3-methyl-1,5-pentanediol, the dicarboxylic acid component was 67 mol% isophthalic acid and 33 mol% adipic acid, and the amount of trimellitic anhydride in all monomers was 1 mol%. Thereafter, the temperature was raised to 200°C over about 4 hours, and then to 230°C over 2 hours, and the reaction was continued until no water was discharged. Thereafter, the mixture was further reacted for 5 hours under a reduced pressure of 10 mmHg to 15 mmHg to obtain [Intermediate Polyester A-3]. Next, into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, [Intermediate Polyester A-3] and isophorone diisocyanate (IPDI) were added in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, and after diluting with ethyl acetate to make a 50% ethyl acetate solution, the mixture was reacted at 100°C for 5 hours to obtain [Prepolymer A-3].

[0209] (Manufacturing example B-1) <Synthesis of prepolymer B-1> In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, 2 mol ethylene oxide adduct of bisphenol A, 2 mol propylene oxide adduct of bisphenol A, terephthalic acid and adipic acid were added together with titanium tetraisopropoxide (1,000 ppm relative to the resin component) so that the molar ratio of hydroxyl group to carboxyl group, OH / COOH, was 1.1, the composition of the diol component was 80 mol% of 2 mol ethylene oxide adduct of bisphenol A, 20 mol% of 2 mol propylene oxide adduct of bisphenol A, and the composition of the dicarboxylic acid component was 60 mol% of terephthalic acid and 40 mol% of adipic acid. After that, the temperature was raised to 200°C in about 4 hours, and then raised to 230°C in 2 hours, and the reaction was carried out until no water was discharged. After that, the reaction was further carried out for 5 hours under a reduced pressure of 10 mmHg to 15 mmHg to obtain [Intermediate Polyester B-1]. Next, the obtained [intermediate polyester B-1] and isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, and after diluting with ethyl acetate to make a 50% ethyl acetate solution, the mixture was reacted at 100°C for 5 hours to obtain [prepolymer B-1].

[0210] (Manufacturing example B-2) <Synthesis of prepolymer B-2> In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, ethylene oxide 2 moles of bisphenol A, propylene oxide 2 moles of bisphenol A, terephthalic acid and adipic acid were added together with titanium tetraisopropoxide (1,000 ppm relative to the resin component) so that the molar ratio of hydroxyl group to carboxyl group, OH / COOH, was 1.1, the composition of the diol component was 80 mol% of ethylene oxide 2 moles of bisphenol A, 20 mol% of propylene oxide 2 moles of bisphenol A, and the composition of the dicarboxylic acid component was 30 mol% of terephthalic acid and 70 mol% of adipic acid. After that, the temperature was raised to 200°C in about 4 hours, and then raised to 230°C in 2 hours, and the reaction was carried out until no water was discharged. After that, the reaction was further carried out for 5 hours under a reduced pressure of 10 mmHg to 15 mmHg to obtain [intermediate polyester B-2]. Next, the obtained [intermediate polyester B-2] and isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, and after diluting with ethyl acetate to make a 50% ethyl acetate solution, the mixture was reacted at 100°C for 5 hours to obtain [prepolymer B-2].

[0211] (Manufacturing example B-3) <Synthesis of prepolymer B-3> In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, ethylene oxide 2 moles of bisphenol A, propylene oxide 2 moles of bisphenol A, terephthalic acid and adipic acid were added together with titanium tetraisopropoxide (1,000 ppm relative to the resin component) so that the molar ratio of hydroxyl group to carboxyl group, OH / COOH, was 1.1, the composition of the diol component was 80 mol% of ethylene oxide 2 moles of bisphenol A, 20 mol% of propylene oxide 2 moles of bisphenol A, and the composition of the dicarboxylic acid component was 80 mol% of terephthalic acid and 20 mol% of adipic acid. After that, the temperature was raised to 200°C in about 4 hours, and then raised to 230°C in 2 hours, and the reaction was carried out until no water was discharged. After that, the reaction was further carried out for 5 hours under a reduced pressure of 10 mmHg to 15 mmHg to obtain [Intermediate Polyester B-3]. Next, the obtained [intermediate polyester B-3] and isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, and after diluting with ethyl acetate to make a 50% ethyl acetate solution, the mixture was reacted at 100°C for 5 hours to obtain [prepolymer B-3].

[0212] (Manufacturing example C-1) <Synthesis of amorphous polyester resin C-1> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, bisphenol A ethylene oxide side 2 mole adduct, bisphenol A propylene oxide 3 mole adduct, terephthalic acid, adipic acid, and trimethylolpropane were added to form a mixture in which the molar ratio of bisphenol A ethylene oxide side 2 mole adduct to bisphenol A propylene oxide 3 mole adduct (bisphenol A ethylene oxide side 2 mole adduct / bisphenol A propylene oxide 3 mole adduct) was 85 / 15, and the molar ratio of terephthalic acid to adipic acid was 1.0. The monomers were charged so that the molar ratio (terephthalic acid / adipic acid) was 75 / 25, the amount of trimethylolpropane in the total monomers was 1 mol%, and the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.2, and reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for a further 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and reacted at 180°C and normal pressure for 3 hours to obtain [Amorphous Polyester Resin C-1].

[0213] (Manufacturing example C-2) <Synthesis of amorphous polyester resin C-2> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, bisphenol A ethylene oxide side 2 mole adduct, bisphenol A propylene oxide 3 mole adduct, terephthalic acid, adipic acid, and trimethylolpropane were added to form a mixture in which the molar ratio of bisphenol A ethylene oxide side 2 mole adduct to bisphenol A propylene oxide 3 mole adduct (bisphenol A ethylene oxide side 2 mole adduct / bisphenol A propylene oxide 3 mole adduct) was 85 / 15, and the molar ratio of terephthalic acid to adipic acid was 1.0. The monomers were charged so that the molar ratio (terephthalic acid / adipic acid) was 65 / 35, the amount of trimethylolpropane in the total monomers was 1 mol%, and the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.2, and reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for another 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and reacted at 180°C and normal pressure for 3 hours to obtain [Amorphous Polyester Resin C-2].

[0214] (Manufacturing example C-3) <Synthesis of amorphous polyester resin C-3> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, bisphenol A ethylene oxide side 2 mole adduct, bisphenol A propylene oxide 3 mole adduct, terephthalic acid, adipic acid, and trimethylolpropane were added to form a mixture in which the molar ratio of bisphenol A ethylene oxide side 2 mole adduct to bisphenol A propylene oxide 3 mole adduct (bisphenol A ethylene oxide side 2 mole adduct / bisphenol A propylene oxide 3 mole adduct) was 85 / 15, and the molar ratio of terephthalic acid to adipic acid was 1.0. The monomers were charged so that the molar ratio (terephthalic acid / adipic acid) was 85 / 15, the amount of trimethylolpropane in the total monomers was 1 mol%, and the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.2, and reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for a further 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and reacted at 180°C and normal pressure for 3 hours to obtain [Amorphous Polyester Resin C-3].

[0215] (Manufacturing example C-4) <Synthesis of amorphous polyester resin C-4> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, bisphenol A ethylene oxide side 2 mole adduct, bisphenol A propylene oxide 3 mole adduct, terephthalic acid, adipic acid, and trimethylolpropane were added to form a mixture in which the molar ratio of bisphenol A ethylene oxide side 2 mole adduct to bisphenol A propylene oxide 3 mole adduct (bisphenol A ethylene oxide side 2 mole adduct / bisphenol A propylene oxide 3 mole adduct) was 85 / 15, and the molar ratio of terephthalic acid to adipic acid was 1.0. The monomers were charged so that the molar ratio (terephthalic acid / adipic acid) was 60 / 40, the amount of trimethylolpropane in the total monomers was 1 mol%, and the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.2, and reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for another 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and reacted at 180°C and normal pressure for 3 hours to obtain [Amorphous Polyester Resin C-4].

[0216] (Manufacturing example C-5) <Synthesis of amorphous polyester resin C-5> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, bisphenol A ethylene oxide side 2 mole adduct, bisphenol A propylene oxide 3 mole adduct, terephthalic acid, adipic acid, and trimethylolpropane were added. The molar ratio of bisphenol A ethylene oxide side 2 mole adduct and bisphenol A propylene oxide 3 mole adduct was 90 / 10 (bisphenol A ethylene oxide side 2 mole adduct / bisphenol A propylene oxide 3 mole adduct), and the molar ratio of terephthalic acid and adipic acid was 90 / 10. The monomers were charged so that the molar ratio (terephthalic acid / adipic acid) was 75 / 25, the amount of trimethylolpropane in the total monomers was 1 mol%, and the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.2, and reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for another 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and reacted at 180°C and normal pressure for 3 hours to obtain [Amorphous Polyester Resin C-5].

[0217] (Manufacturing example D-1) <Synthesis of crystalline polyester resin D-1> Dodecanedioic acid and 1,6-hexanediol were charged into a 5 L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple so that the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 0.9, and reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at 180°C for 10 hours, then heated to 200°C and reacted for 3 hours, and further reacted at a pressure of 8.3 kPa for 2 hours to obtain [Crystalline Polyester Resin D-1].

[0218] <Preparation of Crystalline Polyester Resin Dispersion> A container equipped with a stirring rod and a thermometer was charged with 50 parts of [Crystalline Polyester Resin D-1] and 450 parts of ethyl acetate. The temperature was raised to 80 °C with stirring and held at 80 °C for 5 hours, then cooled to 30 °C over 1 hour. Using a bead mill (Ultraviscomill, manufactured by Imex Co., Ltd.), dispersion was carried out under the conditions of a liquid feeding rate of 1 kg / hr, a disk peripheral speed of 6 m / sec, 80% by volume filling of zirconia beads with a diameter of 0.5 mm, and 3 passes to obtain [Crystalline Polyester Resin Dispersion 1].

[0219] (Example 1) <Preparation of Masterbatch (MB)> 1,200 parts of water, 500 parts of carbon black (Printex 35 manufactured by Degussa) [DBP oil absorption = 42 mL / 100 mg, pH = 9.5], and 500 parts of [Amorphous Polyester Resin C-1] were added and mixed with a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.). The mixture was kneaded at 150 °C for 30 minutes using two rolls, then rolled and cooled and pulverized with a pelletizer to obtain [Masterbatch 1].

[0220] <Preparation of WAX Dispersion> A container equipped with a stirring rod and a thermometer was charged with 50 parts of paraffin wax (manufactured by Nippon Seiro Co., Ltd., HNP-9, hydrocarbon wax, melting point 75 °C, SP value 8.8) as a mold release agent 1 and 450 parts of ethyl acetate. The temperature was raised to 80 °C with stirring and held at 80 °C for 5 hours, then cooled to 30 °C over 1 hour. Using a bead mill (Ultraviscomill, manufactured by Imex Co., Ltd.), dispersion was carried out under the conditions of a liquid feeding rate of 1 kg / hr, a disk peripheral speed of 6 m / sec, 80% by volume filling of zirconia beads with a diameter of 0.5 mm, and 3 passes to obtain [WAX Dispersion 1].

[0221] <Synthesis of Ketimine Compound> A reaction vessel equipped with a stirring rod and a thermometer was charged with 170 parts of isophoronediamine and 75 parts of methyl ethyl ketone, and the reaction was carried out at 50 °C for 5 hours to obtain [Ketimine Compound 1]. The amine value of [Ketimine Compound 1] was 418.

[0222] <Preparation of Oil Phase> 500 parts of [WAX dispersion 1], 76 parts of [Prepolymer A-1], 152 parts of [Prepolymer B-1], 836 parts of [Amorphous polyester resin C-1], 100 parts of [Master batch 1], and 2 parts of [Ketimine compound 1] as a curing agent and 1.5 parts of [Modified layered inorganic mineral] were placed in a container and mixed at 5,000 rpm for 60 minutes using a TK Homomixer (manufactured by Primix Corporation). After that, a homogenization process was carried out in which the mixture was further dispersed using a bead mill to homogenize the mixture, thereby obtaining [Oil phase 1]. As the "modified layered inorganic mineral" mentioned above, "Clayton APA (manufactured by BYK Japan)" was used.

[0223] <Synthesis of organic fine particle emulsion (fine particle dispersion)> In a reaction vessel equipped with a stirring rod and a thermometer, 683 parts of water, 11 parts of sodium salt of methacrylic acid ethylene oxide adduct sulfate (Eleminol RS-30: manufactured by Sanyo Chemical Industries, Ltd.), 138 parts of styrene, 138 parts of methacrylic acid, and 1 part of ammonium persulfate were charged and stirred at 400 rpm for 15 minutes, resulting in a white emulsion. The mixture was heated to a temperature of 75°C and reacted for 5 hours. Furthermore, 30 parts of a 1% aqueous ammonium persulfate solution was added, and the mixture was aged at 75°C for 5 hours to obtain an aqueous dispersion of a vinyl resin (a copolymer of styrene-methacrylic acid-sodium salt of methacrylic acid ethylene oxide adduct sulfate) [fine particle dispersion 1]. The volume average particle diameter of [Fine Particle Dispersion 1] was measured using an LA-920 (manufactured by HORIBA Corp.) and was found to be 14 μm. A part of [Fine Particle Dispersion 1] was dried to isolate the resin content.

[0224] <Preparation of aqueous phase> 165 parts of water, 12 parts of [microparticle dispersion 1], 23 parts of a 48.5% aqueous solution of sodium dodecyldiphenyletherdisulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.), and 26 parts of ethyl acetate were mixed and stirred to obtain a milky white liquid. This was designated as [aqueous phase 1].

[0225] <Emulsification / solvent removal> 255 parts of [water phase 1] was added to a vessel containing 150 parts of [oil phase 1], and mixed for 20 minutes at 13,000 rpm with a TK homomixer to obtain [emulsified slurry 1]. Next, [emulsified slurry 1] was placed in a vessel equipped with a stirrer and thermometer, and the solvent was removed at 30°C for 8 hours, and then aged at 45°C for 4 hours to obtain [dispersed slurry 1].

[0226] <Washing and drying> 100 parts of [Dispersion Slurry 1] was filtered under reduced pressure, and the following operations were then carried out. (1) 100 parts of ion-exchanged water was added to the filter cake, mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. (2): 100 parts of a 10% aqueous sodium hydroxide solution was added to the filter cake of (1), mixed with a TK homomixer (at 12,000 rpm for 30 minutes), and then filtered under reduced pressure. (3): 100 parts of 10% hydrochloric acid was added to the filter cake of (2), and the mixture was mixed with a TK homomixer (at 12,000 rpm for 10 minutes) and then filtered. (4) 300 parts of 52°C ion-exchanged water was added to the filter cake of (3), mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. The above steps (1) to (4) were repeated twice to obtain a filter cake. The filtered cake was dried in a circulating air dryer at 45° C. for 48 hours, and sieved through a 75 μm mesh to obtain toner base particles 1.

[0227] <External Addition Treatment> 100 parts by mass of [toner base particles 1] were mixed with 0.6 parts by mass of hydrophobic silica having an average particle size of 100 nm, 1.0 parts by mass of titanium oxide having an average particle size of 20 nm, and 0.8 parts of hydrophobic silica fine powder having an average particle size of 15 nm in a Henschel mixer to obtain [toner 1].

[0228] <Preparation of carrier> 100 parts by mass of silicone resin (organo straight silicone), 5 parts by mass of γ-(2-aminoethyl)aminopropyltrimethoxysilane, and 10 parts by mass of carbon black were added to 100 parts by mass of toluene, and dispersed for 20 minutes with a homomixer to prepare a resin layer coating liquid. Using a fluidized bed type coating device, the resin layer coating liquid was applied to the surface of 1,000 parts by mass of spherical magnetite with an average particle size of 50 μm to prepare a [carrier].

[0229] <Preparation of developer> A developer was prepared by mixing 5 parts by weight of [Toner 1] and 95 parts by weight of [Carrier] using a ball mill.

[0230] Example 2 In Example 1, [Prepolymer A-1] was replaced with [Prepolymer A-2] and [Polyester [Toner base particles 2] were obtained in the same manner as in Example 1, except that [polyester resin C-1] was replaced with [polyester resin C-2], 22 parts of a 48.5% aqueous solution of sodium dodecyldiphenyletherdisulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.) was used, and the temperature of the ion-exchanged water in the washing step was changed to 53° C. This [toner base particles 2] was used to produce [toner 2].

[0231] Example 3 In Example 1, [Prepolymer A-1] was replaced with [Prepolymer A-2] and [Polyester [Toner base particle 3] was obtained in the same manner as in Example 1, except that [polyester resin C-1] was replaced with [polyester resin C-3], 24 parts of a 48.5% aqueous solution of sodium dodecyldiphenyletherdisulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.) was used, and the temperature of the ion-exchanged water in the washing step was changed to 55° C. This [toner base particle 3] was used to produce [toner 3].

[0232] Example 4 In Example 1, [Prepolymer A-1] was replaced with [Prepolymer A-3] and [Polyester [Toner base particle 4] was obtained in the same manner as in Example 1, except that [polyester resin C-1] was replaced with [polyester resin C-2], 22 parts of a 48.5% aqueous solution of sodium dodecyldiphenyletherdisulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.) was used, and the temperature of the ion-exchanged water in the washing step was changed to 50° C. This [toner base particle 4] was used to produce [toner 4].

[0233] Example 5 [Toner base particle 5] was obtained in the same manner as in Example 1, except that [Prepolymer A-1] was replaced with 152 parts of [Prepolymer A-3], [Polyester resin C-1] was replaced with 798 parts of [Polyester resin C-3], and 24 parts of a 48.5% aqueous solution of sodium dodecyldiphenyletherdisulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.). [Toner 5] was produced using this [Toner base particle 5].

[0234] Example 6 [Toner base particles 6] were obtained in the same manner as in Example 1, except that [Prepolymer B-1] was replaced with [Prepolymer B-2] in Example 1. [Toner 6] was produced using this [Toner base particles 6].

[0235] Example 7 [Toner base particles 7] were obtained in the same manner as in Example 1, except that [Prepolymer B-1] was replaced with [Prepolymer B-3] in Example 1. [Toner 7] was produced using this [Toner base particles 7].

[0236] Example 8 [Toner base particles 8] were obtained in the same manner as in Example 1, except that 811 parts of [amorphous polyester resin C-1] and 25 parts of [crystalline polyester resin D-1] were added in place of those in Example 1. [Toner 8] was produced using this [toner base particles 8].

[0237] Comparative Example 1 [Toner base particles 9] were obtained in the same manner as in Example 1, except that 40 parts of a 48.5% aqueous solution of sodium dodecyl diphenyl ether disulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.) was used instead. [Toner 9] was produced using this [Toner base particles 9].

[0238] Comparative Example 2 [Toner base particles 10] were obtained in the same manner as in Example 1, except that the homogenization step using a bead mill was omitted. [Toner 10] was produced using this [toner base particles 10].

[0239] Comparative Example 3 [Toner base particles 11] were obtained in the same manner as in Example 1, except that [Prepolymer B-1] was not added and [Polyester resin C-1] was replaced with [Polyester resin C-4] in Example 1. [Toner 11] was produced using this [Toner base particles 11].

[0240] Comparative Example 4 [Toner base particles 12] were obtained in the same manner as in Example 1, except that [Prepolymer A-1] was not added and [Polyester resin C-1] was replaced with [Polyester resin C-5] in Example 1. [Toner 12] was produced using this [Toner base particles 12].

[0241] (measurement) <Toner Tg1st, glass transition temperatures of polyester resins A, B and C> 1 g of toner was put into 100 mL of THF, and Soxhlet extraction was performed to obtain a THF soluble fraction and an insoluble fraction. This was dried in a vacuum dryer for 24 hours, and polyester resin C (a mixture of polyester resin C and crystalline polyester resin D in Example 8) was obtained from the THF soluble fraction, and a mixture of polyester resin A and polyester resin B was obtained from the THF insoluble fraction. These were used as the target samples. In addition, the toner was used as the target sample when measuring the toner Tg1st.

[0242] Next, about 5.0 mg of the target sample was placed in an aluminum sample container, the sample container was placed on a holder unit, and set in an electric furnace. Next, under a nitrogen atmosphere, the sample was heated from -80°C to 150°C at a heating rate of 10°C / min (first heating). After that, the sample was cooled from 150°C to -80°C at a heating rate of 10°C / min, and further heated to 150°C at a heating rate of 10°C / min (second heating). In each of the first and second heating, a DSC curve was measured using a differential scanning calorimeter ("Q-200", manufactured by TA Instruments).

[0243] From the obtained DSC curves, the DSC curve at the first heating was selected using the analysis program in the Q-200 system, and the glass transition temperature Tg1st at the first heating of the target sample was calculated. Similarly, the DSC curve at the second heating was selected, and the glass transition temperature Tg2nd at the second heating of the target sample was calculated.

[0244] <Mass ratio of polyester resins A, B and C> From the THF soluble matter obtained by the Soxhlet extraction, the mass ratio of polyester resin C to crystalline polyester resin D was determined. Also, from the THF insoluble matter obtained by the Soxhlet extraction, the mass ratio of the mixture of polyester resin A and polyester resin B was determined.

[0245] The composition ratio of the toner, Tg1st, Tg2nd, and glass transition temperatures of polyester resins A, B, and C are shown in Table 1.

[0246] (evaluation) The toner and developer obtained above were evaluated as follows. The developer was prepared in the same manner as in Example 1.

[0247] <Low temperature fixability on plain paper> The developer was loaded into the image forming apparatus shown in FIG. 2, and a rectangular solid image of 2 cm×15 cm was printed on PPC paper type 6000<70W>A4 T (manufactured by Ricoh Co., Ltd.) in monochrome mode with a toner adhesion amount of 0.40 mg / cm 2The surface temperature of the fixing roller was changed to observe whether an offset occurred in which the residual image of the solid image was fixed in a place other than the desired place, and the fixing temperature at which cold offset occurred was evaluated. The solid image was formed on the transfer paper at a position 3.0 cm from the leading edge in the paper feed direction. The speed of passing through the nip part of the fixing device was 300 mm / s.

[0248] [Evaluation Criteria] A: The minimum fixing temperature is 130°C or less B: The minimum fixing temperature is greater than 130°C and less than or equal to 135°C. C: The minimum fixing temperature is greater than 135°C and less than 140°C. D: The minimum fixing temperature is higher than 140°C.

[0249] <Heat-resistant storage stability> After storing the toner at 50° C. for 8 hours, it was sieved through a 42 mesh sieve for 2 minutes and the residual ratio on the wire mesh was measured. At this time, the more excellent the heat resistance storage stability of the toner, the smaller the residual ratio. The evaluation criteria for heat-resistant storage stability were as follows:

[0250] [Evaluation Criteria] A: Residual rate is less than 5% B: Residual rate is 5% or more and less than 15% C: Residual rate is 15% or more but less than 30% D: Residual rate is 30% or more

[0251] <Filming of external additives> Using the image forming device, 5,000 sheets (A4 size horizontal) of a vertical band chart with an image area ratio of 30% were output at 3 prints / job in a laboratory environment of 27°C and 90% RH, and then 5,000 sheets (A4 size horizontal) of blank paper were output at 3 prints / job, and then the photoreceptor after printing one halftone image was visually observed. [Evaluation Criteria] A: There is no problem with the photoconductor. There is no problem with the quality. B: There is a slight filming in the direction of the printing, but the level is not significant in terms of image quality, so there is no problem. C: Filming is clearly observed on the photoconductor, and image quality is also at a problematic level.

[0252] <Image blurred> The carrier and toner used in the imagio MP C4300 (manufactured by Ricoh Co., Ltd.) were mixed so that the toner concentration was 5% by mass to obtain a developer. The developer was placed in an imagio MP C4300 (manufactured by Ricoh Co., Ltd.), and 250 sheets of A4-sized originals with a 25% image area ratio were printed in monochrome in succession, and each image was evaluated according to the image graininess evaluation rank. Note that image graininess was evaluated by evaluating the uniformity of the halftone area.

[0253] [Evaluation Criteria] A: No blurring at all, good image quality B: Somewhat blurry, but relatively good image quality C: Somewhat blurry, but still within acceptable image quality D: Image quality is slightly below the acceptable limit (unacceptable) with some blurring.

[0254] [Table 1]

[0255] [Table 2]

[0256] For example, embodiments of the present invention are as follows. (1) A toner for developing an electrostatic image, comprising a toner base and an external additive attached to a surface of the toner base, The toner matrix contains at least a binder resin, a colorant, and a release agent, The external additive contains at least silica, The toner contains a component insoluble in THF and a component soluble in THF, a silica liberation rate A (mass%) from the toner after the treatment under the following conditions satisfies the following relational expression (1), The components of the toner that are insoluble in tetrahydrofuran (THF) are observed at two points, Tga1st and Tgb1st, in the first temperature rise of differential scanning calorimetry (DSC), The toner for developing electrostatic images, wherein the Tga1st is -40°C or more and 10°C or less, and the Tgb1st is 45°C or more and 65°C or less. 0.20≦A<0.55 (1) (conditions) 10 g of the toner and 20 g of the carrier are placed in a 50 mL bottle, and then stirred at 67 Hz for 60 minutes using a rocking mill. (2) The toner according to (1) above, wherein the glass transition temperature (Tgab2nd) at the second temperature rise in differential scanning calorimetry (DSC) of the tetrahydrofuran (THF)-insoluble component of the toner is 0° C. or higher and 50° C. or lower. (3) The toner according to (1) or (2), wherein the glass transition temperature (Tg1st) during the first heating run and the glass transition temperature (Tg2nd) during the second heating run in differential scanning calorimetry (DSC) of the toner satisfy the following relational expression (2): Tg1st-Tg2nd≧10[℃] ···(2) (4) The toner has a glass transition temperature (Tg1st) in the first temperature rise measured by differential scanning calorimetry (DSC) of 45° C. or more and 65° C. or less, The tetrahydrofuran (THF) insoluble component of the toner includes a polyester resin A having a glass transition temperature (Tg2nd) in the second heating step of DSC of -50°C or more and 0°C or less, and a polyester resin B having a glass transition temperature (Tg2nd) in the second heating step of DSC of 45°C or more and 65°C or less, The toner according to any one of (1) to (3), wherein the THF-soluble component of the toner includes a polyester resin C having a DSC second temperature rise glass transition temperature (Tg2nd) of 45° C. or more and 65° C. or less. (5) The toner according to (4) above, wherein when the mass ratio of the polyester resin A to the total mass of the polyester resin A, the polyester resin B, and the polyester resin C is a, the mass ratio of the polyester resin B is b, and the mass ratio of the polyester resin C is c, the a, the b, and the c satisfy the following relational formula (3): 4(a+b) <c ···(3) (6) The toner according to (4) or (5) above, wherein the polyester resin A contains a trivalent or tetravalent aliphatic polyhydric alcohol component having 3 to 10 carbon atoms. (7) The polyester resin A contains a diol component, The toner according to any one of (4) to (6) above, wherein the diol component has an odd number of carbon atoms in the main chain of 3 or more and 9 or less, and has an alkyl group in the side chain. (8) The toner according to any one of the above (4) to (7), wherein the polyester resin A has at least one of a urethane bond and a urea bond. (9) The toner according to any one of the above (4) to (8), wherein the polyester resin B has at least one of a urethane bond and a urea bond. (10) The toner according to any one of the above (4) to (9), wherein the polyester resin C contains a trivalent or tetravalent aliphatic polyhydric alcohol component having 3 to 10 carbon atoms. (11) A toner storage unit, characterized by storing the toner according to any one of (1) to (10) above. (12) A developer comprising the toner according to any one of (1) to (10) above and a carrier. (13) An image forming apparatus comprising: an electrostatic latent image carrier; an electrostatic latent image forming means for forming an electrostatic latent image on the electrostatic latent image carrier; and a developing means having a toner for developing the electrostatic latent image formed on the electrostatic latent image carrier to form a visible image, wherein the toner is the toner described in any one of (1) to (10) above. [Explanation of symbols]

[0257] 10 Photoconductor drum 40 Developer 58 Corona charger 80 Transfer roller 90 Cleaning Equipment 110 Process cartridge 210 Paper feed section 211 Paper feed cassette 212 Paper feed roller 220 Conveyor 221 Lola 222 Timing roller 223 Paper ejection roller 224 Paper output tray 230 Image creation section 231Y, 231C, 231M, 231K Photoconductor Drum 233Y, 233C, 233M, 233K Exposure Unit 240 Transcription Unit 241 Drive roller 242 Driven roller 243 Intermediate transfer belt 244Y, 244C, 244M, 244K Primary transfer roller 245 Secondary opposing roller 246 Secondary transfer roller 250 Fixing unit 251 Fixing belt 252 Pressure roller P paper L exposure [Prior art documents] [Patent documents]

[0258] [Patent Document 1] Japanese Patent Application Publication No. 11-133665 [Patent Document 2] JP 2002-287400 A [Patent Document 3] JP 2002-351143 A [Patent Document 4] Patent No. 2579150 [Patent Document 5] JP 2001-158819 A [Patent Document 6] JP 2004-46095 A [Patent Document 7] JP 2007-271789 A [Patent Document 8] JP 2015-52697 A [Patent Document 9] JP 2015-118151 A [Patent Document 10] JP 2016-164616 A [Patent Document 11] Patent No. 5884797

Claims

1. A toner for developing an electrostatic image, comprising a toner base and an external additive attached to a surface of the toner base, The toner matrix contains at least a binder resin, a colorant, and a release agent, The external additive contains at least silica, The toner contains a component insoluble in THF and a component soluble in THF, A silica liberation rate A (mass%) from the toner after the treatment under the following conditions satisfies the following relational expression (1), The components of the toner that are insoluble in tetrahydrofuran (THF) are observed at two points, Tga1st and Tgb1st, in the first temperature rise of differential scanning calorimetry (DSC). The toner for developing electrostatic images, wherein the Tga1st is from -40°C to 10°C, and the Tgb1st is from 45°C to 65°C. 0.20≦A<0.55 ... (1) (conditions) 10 g of the toner and 20 g of the carrier are placed in a 50 mL bottle, and then stirred at 67 Hz for 60 minutes using a rocking mill.

2. 2. The toner according to claim 1, wherein a glass transition temperature (Tgab2nd) at a second temperature rise in differential scanning calorimetry (DSC) of a component of the toner that is insoluble in tetrahydrofuran (THF) is 0° C. or more and 50° C. or less.

3. 3. The toner according to claim 1, wherein a glass transition temperature (Tg1st) during a first temperature rise and a glass transition temperature (Tg2nd) during a second temperature rise in differential scanning calorimetry (DSC) of the toner satisfy the following relationship (2): Tg1st-Tg2nd≧10[℃]...(2)

4. the toner has a glass transition temperature (Tg1st) in a first temperature rise measured by differential scanning calorimetry (DSC) of 45° C. or higher and 65° C. or lower; The tetrahydrofuran (THF) insoluble component of the toner includes a polyester resin A having a glass transition temperature (Tg2nd) in the second heating step of DSC of −50° C. or more and 0° C. or less, and a polyester resin B having a glass transition temperature (Tg2nd) in the second heating step of DSC of 45° C. or more and 65° C. or less, 3. The toner according to claim 1, wherein the THF-soluble component of the toner contains a polyester resin C having a glass transition temperature (Tg2nd) in a second heating run of DSC of 45° C. or more and 65° C. or less.

5. 5. The toner according to claim 4, wherein a, b, and c satisfy the following relational expression (3), where a is a mass ratio of the polyester resin A, b is a mass ratio of the polyester resin B, and c is a mass ratio of the polyester resin C relative to a total mass of the polyester resin A, the polyester resin B, and the polyester resin C: 4(a+b)<c...(3)

6. 5. The toner according to claim 4, wherein the polyester resin A contains a trivalent or tetravalent aliphatic polyhydric alcohol component having 3 to 10 carbon atoms.

7. The polyester resin A contains a diol component, 5. The toner according to claim 4, wherein the diol component has an odd carbon number of 3 to 9 inclusive in the main chain, and has an alkyl group in the side chain.

8. The toner according to claim 4 , wherein the polyester resin A has at least one of a urethane bond and a urea bond.

9. The toner according to claim 4 , wherein the polyester resin B has at least one of a urethane bond and a urea bond.

10. 5. The toner according to claim 4, wherein the polyester resin C contains a trivalent or tetravalent aliphatic polyhydric alcohol component having 3 to 10 carbon atoms.

11. A toner storage unit, comprising the toner according to claim 1 or 2 stored therein.

12. A developer comprising the toner according to claim 1 or 2 and a carrier.

13. 3. An image forming apparatus comprising: an electrostatic latent image carrier; electrostatic latent image forming means for forming an electrostatic latent image on the electrostatic latent image carrier; and developing means having a toner for developing the electrostatic latent image formed on the electrostatic latent image carrier to form a visible image, wherein the toner is the toner according to claim 1 or 2.

Citation Information

Patent Citations

  • Method of treating tip of binding thread of japanese bound booklet

    JP1983084797A

  • Dry toner

    JP1999133665A

  • Method for producing polyester-based polymer

    JP2001158819A

  • Dry toner, manufacturing method for the toner and image forming apparatus using the toner

    JP2002287400A

  • Image forming method

    JP2002351143A